Toner

By using resin A and shape-specific external additive A in the toner, the image defect problem caused by the separation of spherical external additives in the electrophotography is solved, and the long-term stability and high image quality of the toner are achieved.

CN113848689BActive Publication Date: 2025-02-14CANON KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110699116.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-25
Filing Date
2021-06-23
Publication Date
2025-02-14
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

After long-term use of the toner in the conventional electrophotography method, the spherical external additives tend to detach, resulting in defects such as image stripes and image fog.

Method used

Using the external additive A containing toner particles of resin A and the silicon content, the affinity with the surface of the toner particles is improved by the characteristics of resin A and the shape factor of the external additive A, thereby inhibiting the detachment of the external additive.

Benefits of technology

It effectively inhibits the separation of spherical external additives, prevents image stripes and image fog, and improves the long-term use stability of toner.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113848689B_ABST
    Figure CN113848689B_ABST
Patent Text Reader

Abstract

The present invention relates to a toner. A toner comprising toner particles and an external additive A, wherein the toner particles contain a resin A, wherein the resin A is a resin represented by the following formula (1), the resin A is present on the surface of the toner particles, the external additive A is a fine particle containing silicon, the shape factor SF-1 of the external additive A has an average value of 105 to 120, the shape factor SF-2 of the external additive A has an average value of 100 to 130,
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a toner used in a recording method using electrophotography or the like. Background Art

[0002] In recent years, as the purpose of use and the use environment of image forming apparatuses such as copiers and printers have become diversified, longer life and higher image quality have been required.

[0003] As an image forming method, various methods are known, but among them, electrophotography is the main technology. The process carried out in the electrophotography is as follows. First, an electrostatic latent image is formed on an electrostatic charge image bearing member (hereinafter also referred to as a "photosensitive member") using various methods. Next, the latent image is converted into a visible image by developing with a developer (hereinafter also referred to as a "toner"), and the toner image is transferred to a recording medium such as paper as needed, and the toner image is fixed on the recording medium by heat, pressure, etc., so as to obtain a copy.

[0004] In these toners, functional particles such as fine silica particles are usually added externally to the toner particle surface to obtain high image quality. However, because the functional particles become embedded in the toner particle surface over a long period of use, the characteristics of the toner gradually change. In particular, if the fluidity of the toner decreases, toner aggregation is likely to occur, the aggregated toner becomes fixed to components such as a photosensitive member and a developing blade, and an image defect known as an image streak occurs.

[0005] As a technology for solving this problem, Japanese Patent Application Publication Nos. 2017-032598 and H04-050859 disclose ways of reducing embedding of functional particles by using spherical silica fine particles or spherical silicone fine particles as spacers. Summary of the invention

[0006] The spherical external additive can not only disperse the embedding pressure to achieve planar contact with the surface of the toner particle, but the external additive itself is also effective in functioning as a bearing so that the fluidity can be improved. However, when externally added, since the mechanical impact given to fix the external additive is dispersed, it is difficult to fix the external additive to the surface of the toner particle, and as a result of long-term use, the spherical external additive itself migrates to other members.

[0007] Therefore, it is impossible to completely solve problems such as image streaks because of the decrease in fluidity caused by long-term use. In addition, in the case where the migrated spherical external additive contaminates charging-related members such as a developing blade, an image defect known as image fogging occurs. Therefore, a technology that can sufficiently suppress this migration even when a spherical external additive is used is required.

[0008] The present disclosure provides a toner in which detachment of a spherical external additive is suppressed even after long-term use, and image streaks and image fogging can be suppressed.

[0009] The present disclosure relates to a toner comprising:

[0010] Toner particles comprising resin A, and

[0011] External additive A, wherein

[0012] Resin A is a resin represented by the following formula (1),

[0013] Resin A is present on the surface of toner particles.

[0014] The external additive A is fine particles containing silicon,

[0015] The average value of the shape factor SF-1 of the external additive A is 105 to 120,

[0016] The average value of the shape factor SF-2 of the external additive A is 100 to 130,

[0017] In formula (1), P 1 Indicates polymer segment, L 1 represents a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -OR 4 -、-NH-、-NHR 5 - or phenylene; R 4 and R 5 Each is independently an alkylene group or a phenylene group having 1 to 4 carbon atoms, and each carbon atom may have a hydroxyl group as a substituent;

[0018] R 1 To R 3 At least one of them is hydroxyl or alkoxy, R 1 To R 3 The remainder of each independently represents a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, an aryl group or a hydroxyl group;

[0019] m is a positive integer, and

[0020] When the value of m is 2 or more, multiple L 1Parts (moieties), multiple R 1 Partial, multiple R 2 Partial and Multiple R 3 The parts may be the same as or different from each other.

[0021]

[0022] According to the present disclosure, a toner can be provided in which detachment of a spherical external additive is suppressed even after long-term use and image streaks and image fogging can be suppressed. Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION

[0023] Embodiments will now be described in detail, but the present invention is by no means limited to the description given below. In the present disclosure, unless otherwise specified, the description "from XX to YY" and "XX to YY" indicating a numerical range means a numerical range including its lower limit and upper limit as endpoints.

[0024] "Monomer unit" refers to the reacted form of a monomer substance in a polymer or resin.

[0025] When a numerical range is described in stages, the upper limit and the lower limit of each numerical range can be arbitrarily combined.

[0026] The present disclosure relates to a toner comprising

[0027] Toner particles comprising resin A, and

[0028] External additive A, wherein

[0029] Resin A is a resin represented by the following formula (1),

[0030] Resin A is present on the surface of toner particles.

[0031] The external additive A is fine particles containing silicon,

[0032] The average value of the shape factor SF-1 of the external additive A is 105 to 120,

[0033] The shape factor SF-2 of the external additive A was 100 to 130 on average.

[0034] (In formula (1), P 1 Indicates the polymer part, L 1 represents a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -OR 4 -、-NH-、-NHR 5 - or phenylene. 4 and R 5Each is independently an alkylene group or a phenylene group having 1 to 4 carbon atoms, and each carbon atom may have a hydroxyl group as a substituent. 1 To R 3 At least one of them is hydroxyl or alkoxy, R 1 To R 3 The rest of L in each independently represents a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, an aryl group or a hydroxyl group. m is a positive integer, and when the value of m is 2 or more, a plurality of L 1 Partial, multiple R 1 Partial, multiple R 2 Partial and Multiple R 3 The parts may be the same as or different from each other.)

[0035]

[0036] By using the toner, the inventors of the present invention have found that it is possible to provide a toner in which detachment of a spherical external additive is suppressed even after long-term use, and image streaks and image fogging can be suppressed. The reason for this is presumed to be as follows.

[0037] When forming an image, the toner is rubbed by a roller or a developing blade, and the fine particles externally added to the surface of the toner particles are subjected to pressure that causes the fine particles to embed into the interior of the toner particles. Because the spherical external additives undergo a planar contact with the surface of the toner particles compared to the non-spherical external additives, the embedding pressure applied to the external additives is dispersed. Therefore, the spherical external additives are less likely to embed into the interior of the toner particles, and because the spherical external additives act as bearings, the toner fluidity is improved and maintained for a long time. As a result, the toner is less likely to be fixed to the developing member, and image defects such as image streaks are less likely to occur.

[0038] In contrast, since the spherical external additive is less likely to become embedded in the interior of the toner particles, it is difficult to fix the spherical external additive to the surface of the toner particles, and the spherical external additive itself easily migrates to other members as a result of long-term use. Therefore, the migration of the spherical external additive leads to problems such as contamination of the members and reduction in fluidity, and causes image defects such as image streaks and image fogging as a result of long-term use.

[0039] In the above toner, since the resin A contains silicon, when the resin A is present on the surface of the toner particles, the affinity between the resin A and the silicon-containing external additive is improved, and close contact between the toner particles and the external additive is easily generated.

[0040] In addition, in the case where the average value of the shape factor SF-1 of the external addition is 105 to 120 and the average value of the shape factor SF-2 is 100 to 130, the external additive has a property close to a smooth sphere and easily rolls on the surface of the toner particle. In the case where the external additive rolls on the surface of the toner particle, the interface between the tightly bonded toner particles and the external additive is continuously peeled off, and positive peeling charge is generated in the toner particle, and negative peeling charge is generated in the external additive.

[0041] In addition, resin A includes C=O sites and Si-O sites, and these sites are located at L 1 Both sides. 1 is a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -OR 4 -、-NH-、-NHR 5 - or phenylene, and R 4 and R 5 Each is independently an alkylene group or a phenylene group having 1 to 4 carbon atoms. In this case, polarization of the C═O site and polarization of the Si—O site exist within a range in which both sites can generate electrostatic interaction, and charge transfer can be caused.

[0042] As a result of the charge transfer, more electrons are transferred from the resin A to the external additive at the time of stripping charging, which means that the stripping charging between the toner particles and the external additive is further increased. As a result, the electrostatic attraction between the toner particles and the external additive acts sufficiently, and the external additive can be suppressed from detaching from the toner particle surface. Therefore, image streaks and image fogging can be suppressed even after long-term use.

[0043] The toner will now be described.

[0044] First, resin A will be discussed.

[0045] The toner particles contain resin A. Resin A is represented by the following formula (1).

[0046]

[0047] In formula (1), P 1 Indicates the polymer part, L 1 represents a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -OR 4 -、-NH-、-NHR 5 - or phenylene. 4 and R 5 Each is independently an alkylene group or a phenylene group having 1 to 4 carbon atoms, and each carbon atom may have a hydroxyl group as a substituent. 4 -, -NH-, and -NHR5 -, O or N is preferably bonded to the carbonyl group in the formula (1).

[0048] R 1 To R 3 At least one of them is hydroxyl or alkoxy, R 1 To R 3 The rest of L in each independently represents a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, an aryl group or a hydroxyl group. m is a positive integer, and when the value of m is 2 or more, a plurality of L 1 Partial, multiple R 1 Partial, multiple R 2 Partial and Multiple R 3 The parts may be the same as or different from each other.

[0049] In addition, R in formula (1) 1 To R 3 Each independently is preferably an alkoxy group or a hydroxy group.

[0050] The carbon number of the alkyl group is preferably 1-4, and more preferably 1-3.

[0051] The carbon number of the alkoxy group is preferably 1-4, and more preferably 1-3.

[0052] The carbon number of the aryl group is preferably 6-12, and more preferably 6-10.

[0053] In order to make R 1 To R 3 At least one of them is a hydroxyl group. For example, R 1 To R 3 A resin in which at least one of the groups is an alkoxy group is hydrolyzed to convert the alkoxy group into a hydroxyl group.

[0054] Any method may be used for hydrolysis, and the following methods are examples.

[0055] Where R in formula (1) 1 To R 3 The resin in which at least one of the groups is an alkoxy group is dissolved or suspended in a suitable solvent (which may be a polymerizable monomer), the pH is adjusted to acidic using an acid or a base, and mixing and hydrolysis are performed.

[0056] The hydrolysis may also be performed during the production of the toner particles.

[0057] In formula (1), P 1 It is a polymer segment. Examples here are a polyester segment, a vinyl polymer segment (for example, a styrene-acrylic copolymer segment), a polyurethane segment, a polycarbonate segment, a phenolic resin segment, and a polyolefin segment.

[0058] P in formula (1) 1 By configuring in this manner, the polarization of the C═O site derived from the polyester site can also contribute to the electrostatic interaction with the polarization of the Si—O site, and thus the detachment of the spherical external additive can be more effectively suppressed.

[0059] The P in formula (1) is given 1 Further description of the embodiments comprising polyester moieties, but the invention is not limited thereto.

[0060] The polyester part refers to a polymer part having an ester bond (-CO-O-) in the main chain repeating unit. An example here is a condensation polymer structure between a polyol (alcohol component) and a polycarboxylic acid (carboxylic acid component). A specific example is a polymer part in which a structure represented by the following formula (4) (structure derived from a dicarboxylic acid) is bonded to form an ester bond with at least one structure (structure derived from a diol) selected from the group consisting of formulas (5) to (7) given below. This can also be a polymer part in which a structure represented by the following formula (8) (structure derived from a compound having a carboxyl group and a hydroxyl group in a single molecule) is bonded to form an ester bond.

[0061] In addition to those mentioned above, the following monomers disclosed with respect to the polyester resin may be used in the polyester portion.

[0062]

[0063] (In formula (4), R 6 represents an alkylene group, an alkenylene group, or an arylene group. )

[0064]

[0065] (In formula (5), R 7 represents an alkylene group or a phenylene group. )

[0066]

[0067] (In formula (6), R 8 The parts each independently represent ethylene or propylene. x and y each independently represent an integer greater than 0, and the average value of x+y is 2 to 10. )

[0068]

[0069]

[0070] (In formula (8), R 9 represents an alkylene group or an alkenylene group. )

[0071] In formula (4), R6 The alkylene group (preferably having 1 to 12 carbons) represented by can be exemplified by the following:

[0072] methylene, ethylene, trimethylene, propylene, tetramethylene, hexamethylene, neopentylene, heptamethylene, octamethylene, nonamethylene, decamethylene, undecamethylene, dodecamethylene, 1,3-cyclopentylene, 1,3-cyclohexylene, and 1,4-cyclohexylene.

[0073] In formula (4), R 6 The alkenylene group (preferably having 2 to 4 carbons) represented can be exemplified by vinylene, propenylene, and 2-butenylene.

[0074] In formula (4), R 6 The arylene group (preferably having 6 to 12 carbons) represented by can be exemplified by 1,4-phenylene, 1,3-phenylene, 1,2-phenylene, 2,6-naphthylene, 2,7-naphthylene, and 4,4′-biphenylene.

[0075] R in formula (4) 6 May be substituted with a substituent. Examples of the substituent in this case are a methyl group, a halogen atom, a carboxyl group, a trifluoromethyl group, and combinations thereof.

[0076] In formula (5), R 7 The alkylene group (preferably having 1 to 12 carbons) represented by can be exemplified by the following:

[0077] methylene, ethylene, trimethylene, propylene, tetramethylene, hexamethylene, neopentylene, heptamethylene, octamethylene, nonamethylene, decamethylene, undecamethylene, dodecamethylene, 1,3-cyclopentylene, 1,3-cyclohexylene, and 1,4-cyclohexylene.

[0078] In formula (5), R 7 The phenylene group represented by can be exemplified by 1,4-phenylene, 1,3-phenylene, and 1,2-phenylene.

[0079] R in formula (5) 7 May be substituted with a substituent. Examples of the substituent in this case are a methyl group, an alkoxy group, a hydroxyl group, a halogen atom, and combinations thereof.

[0080] In formula (8), R 9 The alkylene group (preferably having 1 to 12 carbon atoms) represented by can be exemplified by the following:

[0081] methylene, ethylene, trimethylene, propylene, tetramethylene, hexamethylene, neopentylene, heptamethylene, octamethylene, nonamethylene, decamethylene, undecamethylene, dodecamethylene, and 1,4-cyclohexylene.

[0082] In formula (8), R 9 The alkenylene group (preferably having 2 to 40 carbons) represented by can be exemplified by the following:

[0083] ethenylene, propenylene, butenylene, butadienylene, pentenylene, hexenylene, hexadienylene, heptenylene, octenylene, decenylene, octadecenylene, eicosenylene, and triacontenylene.

[0084] These alkenylene groups may have any of the following structures: linear, branched, and cyclic. The position of the double bond may be anywhere, and at least one double bond may exist.

[0085] R in formula (8) 9 Examples of the substituent in this case are an alkyl group, an alkoxy group, a hydroxyl group, a halogen atom, and combinations of the foregoing.

[0086] L in formula (1) 1 Examples of include structures represented by the following formulae (3) and (9), but L 1 There is no particular limitation to these. 1 A structure represented by the following formula (3) is preferred.

[0087]

[0088] (In formula (3), * represents the bonding site with C=O in formula (1), and ** represents the bonding site with Si, R 20 represents an alkylene group or a phenylene group having 1 to 4 carbon atoms, and each carbon atom may have a hydroxyl group as a substituent)

[0089] *-OR 21 -** (9)

[0090] (In formula (9), R 21 represents an alkylene group or a phenylene group having 1 to 4 carbon atoms, and each carbon atom may have a hydroxyl group as a substituent. * represents a bonding site with C=O in formula (1), and ** represents a bonding site with Si in formula (1).

[0091] The structure represented by formula (3) is a divalent linking group that forms an amide bond together with C═O in formula (1).

[0092] The linking group is not limited to the case where it is formed by reaction. In the case where the linking group is formed by reaction to generate a resin represented by formula (1), for example, a compound having a carboxyl group may react with an aminosilane compound (e.g., a compound comprising an amino group and an alkoxysilyl group, a compound comprising an amino group and an alkylsilyl group, etc.).

[0093] The aminosilane compound is not particularly limited, but examples thereof include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-phenyl-γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, N-6-(aminohexyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethylsilane, and 3-aminopropylsilane.

[0094] R in formula (3) 20 The included alkylene group may be an alkylene group including an -NH- group.

[0095] The structure represented by formula (3) may be a divalent linking group that forms a urethane bond together with C═O in formula (1).

[0096] The linking group is not limited to the case where it is formed by reaction. In the case where the linking group is formed by reaction to generate a resin represented by formula (1), for example, a compound having a hydroxyl group may react with an isocyanatosilane compound (e.g., a compound comprising an isocyanate group and an alkoxysilyl group, a compound comprising an isocyanate group and an alkylsilyl group, etc.).

[0097] The isocyanatosilane compound is not particularly limited, but examples thereof include 3-isocyanatopropyltrimethoxysilane, 3-isocyanatopropylmethyldimethoxysilane, 3-isocyanatopropyldimethylmethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropylmethyldiethoxysilane, 3-isocyanatopropyldimethylethoxysilane, and 3-isocyanatopropyltrimethylsilane.

[0098] Now we will give the P in formula (1) 1 is an example of an embodiment of a vinyl polymer moiety.

[0099] Resin A can be obtained by vinyl polymerization of a vinyl compound and a silicon-containing vinyl compound. Methyl acrylate, ethyl acrylate, butyl acrylate, octyl acrylate, dimethylaminoethyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dimethylaminoethyl methacrylate, and vinyl acetate can be used as the vinyl compound.

[0100] 3-Methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, and the like can be used as the silicon-containing vinyl compound.

[0101] Resin A can be obtained by vinyl polymerization of these. In such cases, other components can be polymerized to control properties. For example, styrene, substituted styrene compounds such as vinyl toluene, substituted vinyl naphthalene compounds, ethylene, propylene, vinyl methyl ether, vinyl ethyl ether, vinyl methyl ketone, butadiene, isoprene, maleic acid, and maleic acid esters can be used.

[0102] The production method of the vinyl polymer is not particularly limited, and a well-known method can be used.One of these polymerizable monomers may be used alone, or a combination of two or more thereof may be used.

[0103] In the above toner, resin A is present on the toner particle surface. This can be confirmed by a high-resolution composition image obtained using TOF-SIMS. The process will be described in detail later.

[0104] There is no particular limitation on the method of making the resin A present on the surface of the toner particles, but examples thereof include the following methods. A method in which the resin A is used in at least a part of the binder resin, and the toner particles are obtained by a well-known method such as a pulverization method. A method in which the resin A is made present on the surface of the toner particles by a method of difference in polarity when the toner particles are obtained in an aqueous medium, such as a suspension polymerization method, a dissolution suspension method, or an emulsion aggregation method. A method in which the core particles of the toner particles are produced by a well-known method, and then a shell is formed from a material containing the resin A to obtain the toner particles.

[0105] Regarding the intensity of detected Si ions, if the total ion count of ions with mass numbers of 1 to 1,800 in measurement of the toner particle surface using a time-of-flight secondary ion mass spectrometer (TOF-SIMS) is taken as 1, the ion count derived from silicon with a mass number of 28 is preferably 0.0010 to 0.0050.

[0106] The weight average molecular weight (Mw) of the resin A is preferably 3,000 to 100,000, and more preferably 3,000 to 60,000. If the Mw value is 3,000 or more, the storability of the toner is good, and if the Mw value is 100,000 or less, the low temperature fixability is improved.

[0107] In addition, the content of silicon atoms in the resin A is preferably 0.02% by mass to 2.00% by mass, and more preferably 0.15% by mass to 1.00% by mass.

[0108] If the content of silicon is 0.02 mass % or more, peeling charging occurs more satisfactorily and durability is improved. When the content of silicon is 2.00 mass % or less, the state of mixing with other materials constituting resin A and toner is improved, and toner particles can be prevented from breaking at the material interface.

[0109] In addition, the content of resin A in the toner particles is preferably 0.1% by mass to 10.0% by mass, and more preferably 0.1% by mass to 7.0% by mass. If the content of resin A is 0.1% by mass or more, peeling charging occurs more satisfactorily, and better durability is achieved. When the content of resin A is 10.0% by mass or less, peeling charging can be maintained at a suitable level, and therefore, it is easy to suppress the decrease in fluidity caused by charging.

[0110] The external additive A will now be discussed.

[0111] The toner contains toner particles and an external additive A. The external additive A contains silicon. The shape factor SF-1 of the external additive A has an average value of 105 to 120, and the shape factor SF-2 of the external additive A has an average value of 100 to 130.

[0112] The shape factor SF-1 is an index showing the degree of roundness of the particle, where a value of 100 is a perfect circle, and as the value increases, the shape of the particle becomes away from a circle and becomes indefinite.

[0113] The shape factor SF-1 of the external additive observed using an electron microscope is preferably 105 to 110.

[0114] The SF-1 value of the external additive can be controlled by controlling parameters in the production process of the external additive, classifying the produced external additive, and the like.

[0115] The shape factor SF-2 is an index showing the degree of unevenness of a particle, wherein a value of 100 is a perfect circle, and as the value increases, the particle has a larger convex portion.

[0116] The shape factor SF-2 of the external additive observed using an electron microscope is preferably 105 to 120.

[0117] The SF-2 value of the external additive can be controlled by controlling parameters in the production process of the external additive, classifying the produced external additive, and the like.

[0118] There is no particular limitation on the external additive A as long as the above-mentioned shape factor is satisfied, and examples thereof include silica fine particles such as sol-gel silica fine particles and fumed silica fine particles, organic silicon polymer fine particles, and combinations thereof. In addition, these fine particles may be surface-treated with a silane coupling agent, a titanium coupling agent, or silicone oil, etc.

[0119] The external additive A is preferably at least silica fine particles and / or silicone polymer fine particles, and more preferably silica fine particles and silicone polymer fine particles.

[0120] The silicone polymer fine particles have constituent units represented by the following formulae (A1) to (A4):

[0121] Ri, Rj, Rk, Rg, Rh and Rm represent an organic group, and are preferably each independently an alkyl group having 1 to 6 (preferably 1 to 3, and more preferably 1 or 2) carbon atoms or a phenyl group.

[0122]

[0123] Among them, the case where the organic silicon polymer fine particles contain a large amount of the structure represented by formula (A3) (hereinafter also referred to as "T3 unit structure") can be used as an external additive, and even when embedding pressure is applied, balanced elasticity can be achieved, thereby deforming to an appropriate degree and effectively dispersing the pressure. That is, particles that can be imparted with fluidity and are less likely to become embedded inside the toner particles can be obtained.

[0124] The organosilicon polymer fine particles are preferably silsesquioxane particles. Preferably, the organosilicon polymer in the organosilicon polymer fine particles has a structure in which silicon atoms and oxygen atoms are alternately bonded, and some of the silicon atoms have a structure consisting of R a SiO 3 / 2 The T3 unit structure is shown. a represents an alkyl group or a phenyl group having 1 to 6 (preferably 1 to 3, and more preferably 1 or 2) carbon atoms.

[0125] In addition, in the silicone polymer fine particles 29 In Si-NMR measurement, the ratio of the peak area derived from silicon having a T3 unit structure to the total area of ​​peaks of all silicon elements contained in the silicone polymer in the silicone polymer fine particles is preferably 0.70 to 1.00, and more preferably 0.90 to 1.00.

[0126] In R a In the case of an alkyl group having 1 to 6 carbon atoms or a phenyl group, detachment of the organic silicon polymer fine particles from the toner particles can be favorably suppressed.

[0127] A description will now be given of the organosilicon compound used for producing the organosilicon polymer fine particles.

[0128] The organosilicon polymer is preferably a condensation polymerization product of an organosilicon compound having a structure represented by the following formula (Z).

[0129]

[0130] (In formula (Z), R a R1, R2 and R3 each independently represent a halogen atom, a hydroxyl group, an acetoxy group or an alkoxy group (preferably having 1 to 3 carbon atoms).

[0131] R a is an organic functional group and is not particularly limited, and preferred examples thereof include a hydrocarbon group (and preferably an alkyl group) and an aryl group (and preferably a phenyl group) having 1 to 6 (preferably 1 to 3, and more preferably 1 or 2) carbon atoms.

[0132] R1, R2 and R3 each independently represent a halogen atom, a hydroxyl group, an acetoxy group or an alkoxy group. These are reactive groups and form a crosslinked structure by hydrolysis, addition polymerization and condensation. In addition, the hydrolysis, addition polymerization and condensation of R1, R2 and R3 can be controlled by adjusting the reaction temperature, reaction time, reaction solvent and pH. In each molecule as in formula (Z), except for R a Organosilicon compounds having three reactive groups (R1, R2 and R3) are also known as trifunctional silanes.

[0133] Examples of the compound represented by formula (Z) include those listed below.

[0134] For example, trifunctional methylsilanes such as p-styryltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyldiethoxymethoxysilane, methylethoxydimethoxysilane, methyltrichlorosilane, methylmethoxydichlorosilane, methylethoxydichlorosilane, methyldimethoxychlorosilane, methylmethoxyethoxychlorosilane, methyldiethoxychlorosilane, methyltriacetoxysilane, methyldiacetoxymethoxysilane, methyldiacetoxyethoxysilane, methylacetoxydimethoxysilane, methylacetoxymethoxyethoxysilane, methylacetoxydiethoxysilane, methyltrihydroxysilane, methylmethoxydihydroxysilane, methylethoxydihydroxysilane, methyldimethoxyhydroxysilane, methylethoxymethoxyhydroxysilane and methyldiethoxyhydroxysilane; For example, trifunctional ethylsilanes such as ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrichlorosilane, ethyltriacetoxysilane and ethyltrihydroxysilane; trifunctional propylsilanes such as propyltrimethoxysilane, propyltriethoxysilane, propyltrichlorosilane, propyltriacetoxysilane and propyltrihydroxysilane; trifunctional butylsilanes such as butyltrimethoxysilane, butyltriethoxysilane, butyltrichlorosilane, butyltriacetoxysilane and butyltrihydroxysilane; trifunctional hexylsilanes such as hexyltrimethoxysilane, hexyltriethoxysilane, hexyltrichlorosilane, hexyltriacetoxysilane and hexyltrihydroxysilane; and trifunctional phenylsilanes such as phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrichlorosilane, phenyltriacetoxysilane and phenyltrihydroxysilane. One of these organosilicon compounds may be used alone, or a combination of two or more thereof may be used.

[0135] In addition, the compounds listed below can be used together with the organosilicon compound having the structure represented by formula (Z). Organosilicon compounds having four reactive groups per molecule (tetrafunctional silanes), organosilicon compounds having two reactive groups per molecule (difunctional silanes), and organosilicon compounds having one reactive group per molecule (monofunctional silanes). Examples of these include the compounds listed below.

[0136] For example, trifunctional vinyl silanes such as dimethyldimethoxysilane, dimethyldiethoxysilane, tetraethoxysilane, hexamethyldisilazane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, vinyltriisocyanatosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyldiethoxymethoxysilane, vinylethoxydimethoxysilane, vinylethoxydihydroxysilane, vinyldimethoxyhydroxysilane, vinylethoxymethoxyhydroxysilane and vinyldiethoxyhydroxysilane.

[0137] The content of the structure represented by formula (Z) in the monomer forming the silicone polymer is preferably 50 mol % or more, and more preferably 60 mol % or more.

[0138] The number average particle diameter of the external additive A is preferably 30 nm to 300 nm, and more preferably 50 nm to 200 nm.

[0139] In the case where the number average particle diameter is 30 nm or more, the interface of the toner particles in contact with the external additive A is sufficiently wide, and the embedding of the external additive A into the surface of the toner particles is effectively suppressed. In the case where the number average particle diameter is 300 nm or less, when the external additive A rolls a certain distance on the surface of the toner particles, a sufficient number of rotations is achieved, which means that the surface of the external additive A can be uniformly charged, and the migration of the external additive A can be effectively suppressed.

[0140] In addition, the content of the external additive A in the toner is preferably 0.10 parts by mass to 6.00 parts by mass, more preferably 0.50 parts by mass to 2.50 parts by mass, and further preferably 1.50 parts by mass to 2.20 parts by mass relative to 100 parts by mass of the toner particles.

[0141] When the content is 0.10 parts by mass or more, the external additive A can better impart fluidity to the toner. When the content is 6.00 parts by mass or less, the amount of the external additive A is a suitable amount relative to the toner particles, the occurrence of the external additive A remaining without being fixed can be suppressed, and initial image streaks and image fogging can be suppressed.

[0142] A well-known means can be used for externally adding and fixing the external additive A to the toner particle surface. For example, a Henschel mixer can be used.

[0143] As long as the above-mentioned advantageous effects are not impaired, fine particles other than the external additive A may be used in the toner as needed. By constituting in this manner, for example, fluidity, charging properties, cleaning properties, and the like can be controlled.

[0144] In addition to silica fine particles, examples of external additives include: inorganic oxide fine particles including aluminum oxide fine particles, titanium oxide fine particles, etc.; fine particles of inorganic stearic acid compounds such as aluminum stearate fine particles and zinc stearate fine particles; and fine particles of inorganic titanate compounds such as strontium titanate and zinc titanate.

[0145] As the silica fine particles, both dry silica fine particles known as fumed silica produced by vapor-phase oxidation of silicon halide, and wet silica fine particles produced from water glass or the like can be used.

[0146] In addition, the dry silica fine particles may be composite fine particles of silica and other metal oxides produced by using other metal halides such as aluminum chloride or titanium chloride together with silicon halide in the production process.

[0147] It is preferred to use a silane coupling agent, a titanium coupling agent, a higher fatty acid, a silicone oil, an organosilicon varnish, or various modified organosilicon varnishes, etc. to treat the surface of these inorganic fine particles. One of these surface treatment agents can be used alone, or a combination of two or more thereof can be used. By constituting in this way, the charge amount of the toner can be adjusted and the heat resistance and environmental stability can be improved.

[0148] The total addition amount of external additives other than the external additive A is preferably 0.05 to 10.00 parts by mass, and more preferably 0.1 to 5.0 parts by mass relative to 100 parts by mass of the toner particles. One of these external additives other than the external additive A may be used alone, or a combination of two or more thereof may be used.

[0149] The binder resin will now be discussed.

[0150] The toner may include a binder resin. The binder resin is not particularly limited, and a well-known binder resin may be used.

[0151] The following are examples: for example, homopolymers of aromatic vinyl compounds such as styrene and vinyltoluene and their substitutes; for example, styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl Copolymers of aromatic vinyl compounds such as ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; homopolymers of aliphatic vinyl compounds such as ethylene and propylene and their substitution products; vinyl resins such as polyvinyl acetate, polyvinyl propionate, polyvinyl benzoate, polyvinyl butyrate, polyvinyl formate, and polyvinyl butyral; vinyl ether resins; vinyl ketone resins; acrylic polymers; methacrylic polymers; silicone resins; polyester resins; polyamide resins; epoxy resins; phenolic resins; rosin; modified rosin; and terpene resins. One of these may be used alone, or a combination of a plurality of them may be used.

[0152] Vinyl copolymers of aromatic vinyl compounds, acrylic polymerizable monomers, methacrylic polymerizable monomers, and the like listed below can be used in the copolymer of aromatic vinyl compounds.

[0153] Examples of aromatic vinyl compounds and their substitution products include the following:

[0154] Styrene and styrene derivatives, for example, styrene, α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, p-n-butylstyrene, p-tert-butylstyrene, p-n-hexylstyrene, p-n-octylstyrene, p-n-nonylstyrene, p-n-decylstyrene, p-n-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene.

[0155] The polymerizable monomers used to form the acrylic polymer can be exemplified by acrylic polymerizable monomers such as acrylic acid, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-nonyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethyl phosphate ethyl acrylate, diethyl phosphate ethyl acrylate, dibutyl phosphate ethyl acrylate, and 2-benzoyloxyethyl acrylate.

[0156] The polymerizable monomer used to form the methacrylic polymer can be exemplified by methacrylic polymerizable monomers such as methacrylic acid, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, n-nonyl methacrylate, diethyl phosphate ethyl methacrylate, and dibutyl phosphate ethyl methacrylate.

[0157] The condensation polymer between the carboxylic acid component and the alcohol component exemplified below can be used as the polyester resin. The carboxylic acid component can be exemplified by terephthalic acid, isophthalic acid, phthalic acid, fumaric acid, maleic acid, cyclohexanedicarboxylic acid, and trimellitic acid. The alcohol component can be exemplified by bisphenol A, hydrogenated bisphenol, ethylene oxide adduct of bisphenol A, propylene oxide adduct of bisphenol A, glycerol, trimethylolpropane, and pentaerythritol.

[0158] The polyester resin may be a urea group-containing polyester resin. Preferably, for example, the carboxyl groups at the terminal positions of the polyester resin are not blocked.

[0159] For the purpose of enhancing the viscosity change of the toner at high temperature, the binder resin may have a polymerizable functional group. The polymerizable functional group may be exemplified by a vinyl group, an isocyanate group, an epoxy group, an amino group, a carboxyl group, and a hydroxyl group.

[0160] Among them, from the viewpoints of, for example, developing characteristics and fixing properties, the binder resin is preferably a styrene-(meth)acrylic acid copolymer such as a styrene-(meth)acrylic acid alkyl ester copolymer such as a styrene-butyl acrylate copolymer. In addition, there is no particular limitation on the production method of the polymer, and a well-known method can be used.

[0161] In addition, the resin A can be used as a binder resin.

[0162] Wax will now be discussed.

[0163] The toner particles may contain wax. There is no particular limitation, and the following are examples: aliphatic hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, Fischer-Tropsch wax, and paraffin wax; oxides of aliphatic hydrocarbon waxes such as oxidized polyethylene wax and block copolymers thereof; waxes whose main component is a fatty acid ester such as carnauba wax and montanic acid ester wax, and waxes obtained by deacidification of part or all of fatty acid esters such as deacidified carnauba wax; saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brazilenoic acid, eleostearic acid, and octadecatetraenoic acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, wax alcohol, and myristyl alcohol; polyols such as sorbitol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; Saturated fatty acid bisamides such as methylenebisstearic acid amide, ethylenebiscapric acid amide, ethylenebislauric acid amide, and hexamethylenebisstearic acid amide; unsaturated fatty acid amides such as ethylenebisoleamide, hexamethylenebisoleamide, N,N′-dioleyl adipamide, and N,N′-dioleyl sebacic acid amide; aromatic bisamides such as meta-xylene bisstearamide and N,N′-distearylisophthalamide; fatty acid metal salts (generally known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes obtained by grafting aliphatic hydrocarbon waxes with vinyl monomers such as styrene or acrylic acid; partial esters between fatty acids and polyols such as behenyl monoglyceride; and hydroxyl-containing methyl ester compounds obtained, for example, by hydrogenation of vegetable oils. One of these waxes may be used alone, or a combination of two or more may be used.

[0164] Among them, the use of ester wax is preferred. By configuring in this way, the wax easily seeps out of the surface during fixing and reduces winding on the fixing roller. This is because the polarity of the C=O site in the resin A is similar to that of the C=O site in the ester wax.

[0165] Since the resin A shows high affinity for the ester wax, the ester wax melted when the toner is fixed shows affinity for the resin A present near the toner particle surface and aggregates near the toner particle surface, thereby improving the releasability.

[0166] In addition, when the resin A melts during fixing, the resin A has a high affinity for the silicon-containing spherical external additive, which means that the spherical external additive is easily embedded in the interior of the toner particle surface. At this time, the oozing of the ester wax to the toner particle surface is further promoted. Therefore, by using the silicon-containing spherical external additive on the toner particle surface, the advantageous effect of demolding from the fixing roller is significantly increased.

[0167] The ester wax is preferably an ester compound of an aliphatic monohydric alcohol having 6 to 26 (and preferably 18 to 24) carbon atoms and an aliphatic monocarboxylic acid having 6 to 26 (and preferably 18 to 24) carbon atoms.

[0168] In addition, it is preferable to use an aliphatic hydrocarbon wax such as Fischer-Tropsch wax.

[0169] The aliphatic alcohol used to form the ester wax can be exemplified by 1-hexanol, 1-heptanol, 1-octanol, 1-nonanol, 1-decanol, undecanol, lauryl alcohol, myristyl alcohol, 1-hexadecanol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, and lignocerol. The aliphatic carboxylic acid can be exemplified by valeric acid, caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidyl alcohol, behenic acid, and lignoceric acid.

[0170] The content of the wax is preferably 0.5 parts by mass to 30.0 parts by mass relative to 100.0 parts by mass of the binder resin or the polymerizable monomer.

[0171] Colorants will now be discussed.

[0172] The toner may include a colorant. The colorant is not particularly limited, and a known colorant may be used.

[0173] Examples of yellow pigments include yellow iron oxide, and condensed azo compounds such as navel orange yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, and lemon yellow lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples are shown below.

[0174] CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, 180.

[0175] An example of an orange pigment is shown below.

[0176] Permanent Orange GTR, Pyrazolone Orange, Vulcan Orange, Benzidine Orange G, Indanthrene Brilliant Orange RK, and Indanthrene Brilliant Orange GK.

[0177] Examples of red pigments include Indian red, condensed azo compounds such as Permanent Red 4R, Lithol Red, Pyrazolone Red, Apparent Red Calcium Salt, Lake Red C, Lake Red D, Brilliant Magenta 6B, Brilliant Magenta 3B, Eosin Lake, Rhodamine Lake B, and Alizarin Lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples are shown below.

[0178] CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, 254.

[0179] Examples of blue pigments include copper phthalocyanine compounds and derivatives thereof such as basic blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue partial chloride, fast sky blue, and Indanthrene Blue BG, anthraquinone compounds, and basic dye lake compounds, etc. Specific examples are shown below.

[0180] CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, 66.

[0181] Examples of violet pigments include Fast Violet B and Methyl Violet Lake.

[0182] Examples of green pigments include Pigment Green B, Malachite Green Lake, and Final Yellow Green G. Examples of white pigments include zinc white, titanium oxide, antimony white, and zinc sulfide.

[0183] Examples of black pigments include carbon black, aniline black, non-magnetic ferrite, magnetite, and those toned to black by using the above-mentioned yellow colorant, red colorant and blue colorant. These colorants can be used alone or in a mixture, or in the form of a solid solution.

[0184] If necessary, the colorant may be surface treated with a substance that does not hinder polymerization.

[0185] The amount of the colorant is preferably 1.0 part by mass to 15.0 parts by mass relative to 100.0 parts by mass of the binder resin or the polymerizable monomer.

[0186] The charge control agent will now be discussed.

[0187] The toner particles may contain a charge control agent. Known charge control agents may be used as the charge control agent, and a charge control agent that provides a fast friction charging speed and can maintain a certain and stable friction charge amount is preferred. When the toner particles are produced by a polymerization method, a charge control agent that has little polymerization inhibition and substantially no material soluble in an aqueous medium is preferred.

[0188] The charge control agent includes a charge control agent that controls the toner to be negatively chargeable and a charge control agent that controls the toner to be positively chargeable.

[0189] The following are examples of the charge control agent that controls the toner to be negatively chargeable:

[0190] Monoazo metal compounds; acetylacetone-metal compounds; aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, hydroxycarboxylic acids, and metal compounds of dicarboxylic acids; aromatic hydroxycarboxylic acids, aromatic monocarboxylic acids, and aromatic polycarboxylic acids, and their metal salts, anhydrides, and esters; phenol derivatives such as bisphenol; urea derivatives; metal-containing salicylic acid compounds; metal-containing naphthoic acid compounds; boron compounds; quaternary ammonium salts; calixarene; and resin-based charge control agents.

[0191] On the other hand, the following are examples of a charge control agent that controls the toner to be positively chargeable:

[0192] Aniline black and aniline black modified by, for example, fatty acid metal salts; guanidine compounds; imidazole compounds; quaternary ammonium salts such as tributylbenzyl-1-hydroxy-4-naphthalenesulfonate and tetrabutylammonium tetrafluoroborate, and their onium salt analogs such as phosphonium salts, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake-forming agents are exemplified by phosphotungstic acid, phosphomolybdic acid, phosphomolybdic tungstic acid, tannic acid, lauric acid, gallic acid, ferrocyanide and ferrocyanide); metal salts of higher fatty acids; and resin-based charge control agents.

[0193] A single one of these charge control agents may be used, or a combination of two or more may be used. Among these charge control agents, metal-containing salicylic acid-based compounds are preferred, and metal-containing salicylic acid-based compounds in which the metal is aluminum or zirconium are particularly preferred.

[0194] The added amount of the charge control agent is preferably 0.1 parts by mass to 20.0 parts by mass, and more preferably 0.5 parts by mass to 10.0 parts by mass with respect to 100.0 parts by mass of the binder resin.

[0195] In addition, it is preferable to use a polymer or copolymer having a sulfonic acid group, a sulfonate group or a sulfonate ester group as the charge control resin.

[0196] The polymer having a sulfonic acid group, a sulfonate group or a sulfonic acid ester group preferably contains a sulfonic acid group-containing acrylamide monomer or a sulfonic acid group-containing methacrylamide monomer at a copolymerization ratio of 2% by mass or more, and more preferably 5% by mass or more.

[0197] Preferably, the charge control resin has a glass transition temperature (Tg) of 35° C. to 90° C., a peak molecular weight (Mp) of 10,000 to 30,000, and a weight average molecular weight (Mw) of 25,000 to 50,000.

[0198] When such a charge control resin is used, preferred triboelectric charging characteristics can be imparted without adversely affecting the thermal characteristics required for the toner particles. In addition, since the charge control resin contains a sulfonic acid group, the dispersibility of the charge control resin itself in the colorant dispersion liquid and the dispersibility of the colorant are improved, and the tinting power, transparency and triboelectric charging characteristics can be further improved.

[0199] The method of producing the toner particles will now be discussed.

[0200] Known means can be used for the production method of the toner particles. Examples here are dry production methods, i.e., kneading and pulverization methods; and wet production methods, i.e., suspension polymerization methods, dissolution suspension methods, emulsion aggregation methods, and emulsion polymerization aggregation methods. Use of a wet production method is preferred from the viewpoint of narrowing the particle size distribution of the toner particles, improving the average circularity of the toner particles, and producing a core-shell structure.

[0201] For example, when toner particles are produced by a kneading pulverization method, resin A and optional binder resin, wax, colorant, charge control agent, and other additives are fully mixed using a mixer such as a Henschel mixer and a ball mill. Thereafter, various materials are dispersed or dissolved by melt kneading using a heating kneading machine such as a heating roller, a kneading machine, or an extruder, and toner particles are obtained through a cooling and solidification step, a pulverization step, a classification step, and an optional surface treatment step.

[0202] In the pulverizing step, known pulverizing equipment such as a mechanical impact system and a jet system can be used. For the order of the classification step and the surface treatment step, either one can be performed before the other. Based on the consideration of production efficiency, the classification step preferably uses a multi-stage classifier.

[0203] The production of toner particles by a suspension polymerization method as a wet production method is described below.

[0204] A detailed description will now be given of a toner particle production example in which a suspension polymerization method is used, but the embodiment is not limited thereto. The toner particles are preferably toner particles produced using suspension polymerization.

[0205] In the suspension polymerization method, the resin A and the polymerizable monomer for forming the binder resin are dissolved or dispersed to be uniform using a disperser such as a ball mill or an ultrasonic disperser to obtain a polymerizable monomer composition (polymerizable monomer composition preparation step).

[0206] The polymerizable monomer may be exemplified by the polymerizable monomers provided as examples of the polymerizable monomers for forming the above-mentioned vinyl-based copolymer. Wax, a colorant, a charge control agent, a crosslinking agent, a polymerization initiator, and other additives may be optionally added to the polymerizable monomer composition.

[0207] During the polymerization of the polymerizable monomer, a crosslinking agent may be optionally added to control the molecular weight of the binder resin. A compound having two or more polymerizable double bonds is mainly used as the crosslinking agent. Examples are aromatic divinyl compounds such as divinylbenzene and divinylnaphthalene; carboxylates containing two double bonds such as ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, neopentyl glycol diacrylate, 1,3-butanediol diacrylate, 1,3-butenediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, diacrylates of polyethylene glycol #200, #400 and #600, dipropylene glycol diacrylate, polypropylene glycol diacrylate, polyester diacrylate (MANDA, Nippon Kayaku Co., Ltd.), and crosslinkers obtained by changing the acrylate in the foregoing to methacrylate; divinyl compounds such as divinylaniline, divinyl ether, divinyl sulfide, and divinyl sulfone; and compounds having three or more vinyl groups. A single one of these may be used, or a mixture of two or more may be used.

[0208] The amount of the cross-linking agent added is preferably 0.1 to 15.0 parts by mass based on 100 parts by mass of the polymerizable monomer.

[0209] Next, the polymerizable monomer composition is added to a previously prepared aqueous medium, and droplets of the polymerizable monomer composition are formed into a desired toner particle size using a high shear force mixer or a disperser (granulation step).

[0210] The aqueous medium in the granulation step preferably contains a dispersion stabilizer in order to suppress the aggregation of toner particles during the production process, control the particle size of the toner particles, and narrow the particle size distribution.

[0211] Dispersion stabilizers can generally be classified into polymers that generate repulsive forces by steric hindrance, and sparingly water-soluble inorganic compounds that support dispersion stabilization by electrostatic repulsive forces. Fine particles of sparingly water-soluble inorganic compounds are advantageously used because they can be dissolved by acid or alkali, and because they can be easily removed by dissolution by washing with acid or alkali after polymerization.

[0212] When the dispersion stabilizer is a poorly water-soluble inorganic compound, it is preferred to use a dispersion stabilizer containing any of the following: magnesium, calcium, barium, zinc, aluminum, and phosphorus. The dispersion stabilizer more preferably contains any of the following: magnesium, calcium, aluminum, and phosphorus. Specific examples are as follows.

[0213] Magnesium phosphate, tricalcium phosphate, aluminum phosphate, zinc phosphate, magnesium carbonate, calcium carbonate, magnesium hydroxide, calcium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate and hydroxyapatite. When using this type of poorly water-soluble inorganic dispersant, it can be used as it is, or in order to obtain even finer particles, the inorganic dispersant particles generated in the aqueous medium can be used. The situation of using tricalcium phosphate is used as an example, and sodium phosphate aqueous solution can be mixed with calcium chloride aqueous solution to generate water-insoluble calcium phosphate under high-speed stirring, so that dispersion can be made more uniform and finer.

[0214] In the dispersion stabilizer, organic compounds such as polyvinyl alcohol, gelatin, methyl cellulose, methyl hydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch may be used in combination. These dispersion stabilizers are preferably used in an amount of 0.1 to 20.0 parts by mass relative to 100 parts by mass of the polymerizable monomer.

[0215] Surfactants may also be used in an amount of 0.1 to 10.0 parts by mass relative to 100 parts by mass of the polymerizable monomer to miniaturize these dispersion stabilizers. Specifically, commercially available nonionic, anionic, or cationic surfactants may be used. For example, sodium lauryl sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, potassium stearate, or calcium oleate are preferably used.

[0216] After the granulation step or while the granulation step is being performed, the polymerizable monomer present in the polymerizable monomer composition is polymerized, wherein the temperature is preferably set to 50° C. to 90° C. to obtain a toner particle dispersion (polymerization step).

[0217] During the polymerization step, it is preferred to perform sufficient stirring to provide a uniform temperature distribution in the container. When adding a polymerization initiator, any timing and any desired time length may be used for the addition. In addition, in order to obtain the desired molecular weight distribution, the temperature may be raised in the second half of the polymerization reaction, and, in order to remove, for example, unreacted polymerizable monomers and by-products from the system, a portion of the aqueous medium may be removed by distillation in the second half of the reaction or after the reaction is terminated. The distillation process may be carried out at normal pressure or under reduced pressure.

[0218] The polymerization initiator used in the suspension polymerization method preferably has a half-life of 0.5 to 30 hours during the polymerization reaction. When the polymerization reaction is carried out using an addition amount of 0.5 to 20 parts by mass relative to 100 parts by mass of the polymerizable monomer, a polymer having a maximum value between 5000 and 50000 can be obtained. Oil-soluble initiators are generally used as polymerization initiators, and the following are examples.

[0219] For example, azo compounds such as 2,2′-azobisisobutyronitrile, 2,2′-azobis-2,4-dimethylvaleronitrile, 1,1′-azobis(cyclohexane-1-carbonitrile), and 2,2′-azobis-4-methoxy-2,4-dimethylvaleronitrile, and peroxide-based initiators such as acetyl peroxide cyclohexylsulfonyl, diisopropyl peroxycarbonate, decanoyl peroxide, lauroyl peroxide, stearoyl peroxide, propionyl peroxide, acetyl peroxide, tert-butyl peroxy-2-ethylhexanoate, benzoyl peroxide, tert-butyl peroxyisobutyrate, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicumyl peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, tert-butyl peroxypivalate, and cumene hydroperoxide.

[0220] A water-soluble initiator may be optionally used together with the polymerization initiator, and examples thereof are as follows:

[0221] Ammonium persulfate, potassium persulfate, 2,2′-azobis(N,N′-dimethyleneisobutyroamidine) hydrochloride, 2,2′-azobis(2-amidinopropane) hydrochloride, azobis(isobutylamidine) hydrochloride, sodium 2,2′-azobisisobutyronitrile sulfonate, ferrous sulfate, or hydrogen peroxide.

[0222] One of these polymerization initiators may be used alone, or two or more thereof may be used in combination. A chain transfer agent, a polymerization inhibitor, and the like may also be added and used to control the degree of polymerization of the polymerizable monomer.

[0223] From the viewpoint of obtaining high-definition and high-resolution images, the particle size of the toner particles is preferably a weight average particle size of 3.0 μm to 10.0 μm. The weight average particle size of the toner particles can be measured using a pore resistance method. For example, the measurement can be performed using a "CoulterCounter Multisizer 3" (Beckman Coulter, Inc.).

[0224] The toner particle dispersion liquid obtained by undergoing the polymerization step is transferred to a filtration step in which solid-liquid separation of the toner particles and the aqueous medium is performed.

[0225] Solid-liquid separation for obtaining toner particles from the resulting toner particle dispersion may be performed using a conventional filtration method. It is preferably followed by further washing, such as by reslurrying or washing with washing water, to remove foreign matter that could not be removed from the toner particle surface previously.

[0226] After sufficient washing, a toner filter cake is obtained by further solid-liquid separation. Toner particles are then obtained by drying using known drying means and separating out a particle fraction having a particle size other than a specific particle size by classification as needed. When completed, the separated particle fraction having a particle size other than a specific particle size can be reused to improve the final yield.

[0227] The toner may be used as a magnetic or nonmagnetic one-component developer, but it may also be mixed with a carrier and used as a two-component developer.

[0228] As the carrier, magnetic particles composed of commonly known materials such as metals such as iron, ferrite, magnetite, and alloys of these metals with metals such as aluminum and lead can be used. Among them, ferrite particles are preferred. Further, a coated carrier obtained by coating the surface of magnetic particles with a coating agent such as a resin, a resin-dispersed carrier obtained by dispersing a fine magnetic body powder in a resin, etc. can be used as the carrier.

[0229] The volume average particle diameter of the carrier is preferably 15 μm to 100 μm, and more preferably 25 μm to 80 μm.

[0230] Methods for measuring properties related to toner are described below.

[0231] Measurement method of shape factors SF-1 and SF-2 and number average particle size of external additive A

[0232] By observing the toner to which the external additive is externally added using an S-4800 scanning electron microscope (SEM) manufactured by Hitachi, Ltd., the shape factors SF-1 and SF-2 of the external additive A are calculated in the following manner.

[0233] The maximum length, perimeter, and area of ​​the external additives were measured in a field of view at a magnification of 100,000 to 200,000 times using Image-Pro Plus 5.1J image editing software (manufactured by MediaCybernetics).

[0234] SF-1 and SF-2 were calculated using the following formulas: The average values ​​of 100 external additive measurements were determined in this manner, and these average values ​​were taken as SF-1 and SF-2 of the external additive.

[0235] SF-1=(Maximum length of external additive) 2 / Area of ​​external additive × π / 4 × 100

[0236] SF-2 = (circumference of external additive) 2 / Area of ​​external additive × 100 / 4π

[0237] In addition, the average value of 100 external additive samples having a maximum length similar to that of the external additive A was determined, and the average value was taken as the number average particle diameter.

[0238] The means for distinguishing the silicone polymer fine particles and the silica fine particles in the toner will now be discussed.

[0239] Method for extracting resin A from toner particles

[0240] Extraction of the resin A in the toner particles is performed by separating an extract obtained using tetrahydrofuran (THF) by a solvent gradient elution method. The preparation method is given below.

[0241] 10.0 g of toner particles were weighed out and introduced into an extraction thimble (No. 84, Toyo Rosha Kaisha, Ltd.), and set into a Soxhlet extractor. 200 mL of THF was used as a solvent for extraction for 20 hours, and then the solvent was removed from the extract to obtain a solid as a THF-soluble substance. Resin A was contained in the THF-soluble substance. This process was repeated several times to obtain a desired amount of THF-soluble substance.

[0242] Gradient preparative HPLC (LC-20AP high performance gradient preparative system, Shimadzu Corporation; 50 mmφ×250 mm SunFire preparative column, Waters Corporation) was used for the solvent gradient elution method. The following was used: column temperature was 30°C, flow rate was 50 mL / min, acetonitrile was a poor solvent in the mobile phase, and THF was a good solvent. 0.02 g of THF-soluble matter obtained by extraction was dissolved in 1.5 mL of THF, and used as a sample for separation. A composition with 100% acetonitrile was used for the starting mobile phase; then, when 5 minutes passed after the sample injection, the percentage of THF increased by 4% per minute; and the mobile phase composition at 25 minutes was 100% THF. The components can be separated by drying the obtained fractions until solidified. Resin A can thereby be obtained. The silicon atom content can be measured and 13 C-NMR measurement was used to determine which grades of components were Resin A.

[0243] Method for measuring silicon atom content in resin A

[0244] An "Axios" wavelength dispersive x-ray fluorescence analyzer (PANalytical BV) was used for the silicon atom content in the resin A. The attached "SuperQ ver. 4.0F" (PANalytical BV) software was used to set the measurement conditions and analyze the measurement data.

[0245] Rh was used for the x-ray tube anode, and 24 kV and 100 mA were used for the accelerating voltage and current, respectively.

[0246] Vacuum was used for the measurement atmosphere; 27 mm was used for the measurement diameter (collimator diameter); and 10 seconds was used for the measurement time. For the detector, a proportional counter (PC) was used. The measurement was performed using a PET analysis crystal; the count rate (unit: cps) of Si-Kα rays observed at a diffraction angle (2θ) = 109.08° was measured; and the calibration curve described below was used for determination.

[0247] The resin A may be used as a measurement sample as it is, or a resin extracted from toner particles using the aforementioned extraction method may be used as a measurement sample.

[0248] The pellets for measurement were obtained using a "BRE-32" tablet forming machine (Maekawa Testing Machine Mfg. Co., Ltd.). 4 g of the measurement sample was introduced into a dedicated aluminum press ring and smoothed over, and pellets were produced by forming into a thickness of 2 mm and a diameter of 39 mm by pressing at 20 MPa for 60 seconds, and the pellets were used as the pellets for measurement.

[0249] For the pellets used to prepare the calibration curve for determining the content, the amount of the pellets was calculated relative to 100 parts by mass of the binder [product name: Spectro Blend, composition: C 81.0, O 2.9, H 13.5, N 2.6 (mass %), chemical formula: C 19 H 38 ON, form: powder (44 μm), from Rigaku Corporation] was added in an amount of 0.5 parts by mass of SiO2 (hydrophobic fumed silica) [product name: AEROSIL NAX50, specific surface area: 40±10 (m 2 / g), carbon content: 0.45 to 0.85%, from Nippon Aerosil Co., Ltd.]; thoroughly mixed in a coffee grinder; and pellets were prepared by pellet forming. SiO2 was used at 5.0 parts by mass and 10.0 parts by mass, respectively, and pellets were prepared using the same mixing and pellet forming steps.

[0250] A calibration curve in the form of a linear function is obtained by placing the obtained x-ray count rate on the vertical axis and placing each calibration curve with the Si addition concentration in the sample on the horizontal axis.

[0251] Then, the counting rate of Si-Kα rays is also measured for the measurement sample using the same procedure. The silicon atom content (mass %) is determined from the calibration curve that has been prepared.

[0252] Identification of the structure of resin A

[0253] use 1 H-NMR analysis, 13 C-NMR analysis, 29 Si-NMR analysis and FT-IR analysis were used to determine the polymer site P in the resin A. 1 , L 1 Part, and R 1 To R 3 Structural confirmation of the site.

[0254] The resin A may be used as a measurement sample as it is, or the resin A extracted from toner particles using the above-described extraction method may be used as a measurement sample.

[0255] When L 1 When the amide bond represented by formula (2) is included, 1 Identification can be performed by H-NMR analysis. Specifically, identification can be performed using the chemical shift value of the proton in the NH site in the amide group, and the amount of the amide group can be determined by calculation of the integral value.

[0256] In addition, when R in the resin represented by formula (1) 1 To R 3 When containing alkoxy or hydroxyl groups, the following 29 The valence of the alkoxy group or the hydroxy group relative to the silicon atom was determined by the method described in "Measurement conditions of Si-NMR (solid state)".

[0257] 29 Measurement conditions of Si-NMR (solid state)

[0258] Instrument: JNM-ECX500II, JEOL Resonance, Inc.

[0259] Sample tube: 3.2mmφ

[0260] Sample size: 150 mg

[0261] Measuring temperature: room temperature

[0262] Pulse mode: CP / MAS

[0263] Measurement core frequency: 97.38MHz( 29 Si)

[0264] Reference substance: DSS (external standard: 1.534ppm)

[0265] Sample rotation rate: 10kHz

[0266] Contact time: 10ms

[0267] Delay time: 2s

[0268] Scan times: 2000 to 8000 times

[0269] This measurement makes it possible to obtain the abundance ratio by peak separation / integration through curve fitting of the polysilane component depending on the number of oxygen atoms bonded to Si. Performing in this manner makes it possible to confirm that R in the resin represented by formula (1) 1 To R 3 The valence of the alkoxy or hydroxy group relative to the silicon atom.

[0270] Can be 13 C-NMR (solid state) measurement was used to confirm that P in the resin A represented by formula (1) 1 , L 1 , and R 1 To R 3 The measurement conditions are as follows.

[0271] 13 C-NMR (solid state) measurement conditions

[0272] Instrument: JNM-ECX500II, JEOL Resonance, Inc.

[0273] Sample tube: 3.2mmφ

[0274] Sample size: 150 mg

[0275] Measuring temperature: room temperature

[0276] Pulse mode: CP / MAS

[0277] Measurement core frequency: 123.25MHz( 13 C)

[0278] Reference substance: Adamantane (external standard: 29.5ppm)

[0279] Sample rotation rate: 20kHz

[0280] Contact time: 2ms

[0281] Delay time: 2s

[0282] Scan times: 1024 times

[0283] According to P in formula (1) 1 , L 1 , and R 1 To R 3 The species were separated into various peaks and identified to determine the P 1 , L 1 , and R 1 To R 3 kind of.

[0284] Evaluation method of resin A present on toner particle surface

[0285] Whether or not the resin A is present on the toner particle surface is confirmed by time-of-flight secondary ion mass spectrometry (TOF-SIMS). The equipment and measurement conditions used are as follows.

[0286] Measuring equipment: nanoTOF II (trade name, manufactured by Ulvac-Phi)

[0287] Primary ion type: Bi3 ++

[0288] Accelerating voltage: 30 kV

[0289] Primary ion current: 0.05pA

[0290] Repetition frequency: 8.2kHz

[0291] Raster Mode: Unbunch

[0292] Grating size: 50μm×50μm, 256×256 pixels

[0293] Measuring mode: Positive

[0294] Neutralizing electron gun: Use

[0295] Measuring time: 600 seconds

[0296] Sample preparation: Toner particles immobilized on indium sheets

[0297] Sample pretreatment: None

[0298] Reference sample for identification: Resin A itself or Resin A extracted from toner particles using the aforementioned extraction method.

[0299] By imaging the toner particle surface with the mass numbers of Si ions and fragment ions derived from Resin A using standard software (TOF-DR) produced by Ulvac-Phi, it can be confirmed that Resin A is present in the exposed areas of the toner particle surface.

[0300] Method for measuring number average molecular weight (Mn) and weight average molecular weight (Mw)

[0301] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer, resin or toner particles are measured using gel permeation chromatography (GPC) as follows.

[0302] First, the sample was dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The obtained solution was filtered using a "sample pretreatment box" (Tosoh Corporation) solvent-resistant membrane filter with a pore size of 0.2 μm to obtain a sample solution. The sample solution was adjusted to a concentration of about 0.8% by mass of the THF soluble component. The sample solution was used for measurement under the following conditions.

[0303] Instrument: HLC8120GPC (detector: RI) (Tosoh Corporation)

[0304] Column: Shodex KF-801, 802, 803, 804, 805, 806 and 807 7-column (Showa DenkoKabushiki Kaisha)

[0305] Eluent: Tetrahydrofuran (THF)

[0306] Flow rate: 1.0mL / min

[0307] Oven temperature: 40.0℃

[0308] Sample injection volume: 0.10mL

[0309] A molecular weight calibration curve prepared using polystyrene resin standards (product name: "TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", Tosoh Corporation) is used to determine the molecular weight of the sample.

[0310] Structural evaluation of silicone polymer fine particles

[0311] Solid pyrolysis gas chromatography mass spectrometer (hereinafter referred to as pyrolysis GC / MS) and NMR are used to determine the ratio of the peak area of ​​the T3 unit structure (Formula (A3)) in the organic silicon polymer fine particles contained in the toner, and to identify Rm in Formula (A3).

[0312] In the case where the toner contains silica fine particles in addition to the silicone polymer fine particles, 1 g of the toner is put into a vial, and dissolved and dispersed in 31 g of chloroform. A dispersion is prepared by treating with an ultrasonic homogenizer for 30 minutes to effectively disperse.

[0313] Ultrasonic treatment equipment: VP-050 ultrasonic homogenizer (TIETECH Co., Ltd.)

[0314] Microchip: Stepped microchip, tip diameter 2mmφ

[0315] Microchip tip position: Center of glass vial, 5 mm above the bottom of the vial

[0316] Ultrasonication conditions: 30% intensity, 30 minutes; during this treatment, ultrasonic waves were applied while cooling the vial with ice water to prevent the dispersion from heating up.

[0317] The dispersion was transferred to a glass tube (50 mL) for a swing rotor and centrifuged using a centrifuge (H-9R, Kokusan Co., Ltd.) and 58.33S -1 The centrifugal separation was performed for 30 minutes under the conditions of . After the centrifugal separation, the Si-containing substance other than the organosilicon polymer was contained in the lower layer in the glass tube. The sample was produced by extracting the chloroform solution containing the Si-containing substance derived from the organosilicon polymer in the upper layer and removing the chloroform by vacuum drying (24 hours, 40° C.).

[0318] Using the sample or silicone polymer fine particles obtained above, solid 29 Si-NMR measures and calculates the abundance ratio of the constituent compounds of the silicone polymer fine particles and the proportion of the T3 unit structure in the silicone polymer fine particles.

[0319] Pyrolysis GC / MS was used to analyze the types of constituent compounds of the silicone polymer particles.

[0320] The pyrolysis product components derived from the organosilicon polymer fine particles generated when the organosilicon polymer fine particles are pyrolyzed at about 550° C. to 700° C. are measured by means of mass spectrometry, and by analyzing the decomposition peaks, the kind of compound constituting the organosilicon polymer fine particles can be identified.

[0321] Pyrolysis GC / MS measurement conditions

[0322] Pyrolysis instrument: JPS-700 (Japan Analytical Industry Co., Ltd.)

[0323] Pyrolysis temperature: 590℃

[0324] GC / MS instrument: Focus GC / ISQ (Thermo Fisher)

[0325] Column: HP-5MS, 60m length, 0.25mm inner diameter, 0.25μm film thickness

[0326] Inlet temperature: 200℃

[0327] Flow pressure: 100kPa

[0328] Split flow: 50mL / min

[0329] MS ionization: EI

[0330] Ion source temperature: 200°C, mass range: 45 to 650

[0331] Then, use the solid state 29 Si-NMR measures and calculates the existence ratio of the identified constituent compounds of the organic silicon polymer fine particles. 29 In Si-NMR, peaks are detected in different shift regions depending on the structure of the functional group bonded to Si in the constituent compound of the organic silicon polymer particles.

[0332] By using the standard sample to identify the peak position, the structure bonded to Si can be specified. In addition, the abundance ratio of each constituent compound can be calculated from the obtained peak area. The ratio of the peak area of ​​the T3 unit structure to the total peak area can be determined by calculation.

[0333] Solid State 29 Si-NMR measurement conditions are as follows, for example.

[0334] Equipment: JNM-ECX500II manufactured by JEOLRESONANCE

[0335] Measuring temperature: room temperature

[0336] Measurement method: DDMAS method, 29 Si, 45°

[0337] Sample tube: Zirconia 3.2mmφ

[0338] Sample: Fill the sample tube in powder form

[0339] Sample rotation rate: 10kHz

[0340] Relaxation delay: 180s

[0341] Scan times: 2,000 times

[0342] After this measurement, the organic silicon polymer was peak-separated into the following X1 structure, X2 structure, X3 structure, and X4 structure by curve fitting of silane components having different substituents and bonding groups, and each of their peak areas was calculated.

[0343] The X3 structure shown below is a T3 unit structure.

[0344] X1 structure: (Ri)(Rj)(Rk)SiO 1 / 2 (A1)

[0345] X2 structure: (Rg)(Rh)Si(O 1 / 2 )2 (A2)

[0346] X3 structure: RmSi(O 1 / 2 )3 (A3)

[0347] X4 structure: Si(O 1 / 2 )4 (A4)

[0348]

[0349] In addition, through 13 C-NMR confirmed by R a Represents an organic group.

[0350] 13 C-NMR (solid state) measurement conditions

[0351] Equipment: JNM-ECX500II from JEOL RESONANCE, Inc.

[0352] Sample tube: Zirconia 3.2mmφ

[0353] Sample: Filled in a sample tube in powder form

[0354] Measuring temperature: room temperature

[0355] Pulse mode: CP / MAS

[0356] Measurement core frequency: 123.25MHz( 13 C)

[0357] Reference substance: Adamantane (external standard: 29.5ppm)

[0358] Sample rotation rate: 20kHz

[0359] Contact time: 2ms

[0360] Delay time: 2s

[0361] Scan times: 1024 times

[0362] In this method, R a The hydrocarbon group represented by the present invention is derived from, for example, a silicon-bonded methyl group (Si-CH3), a silicon-bonded ethyl group (Si-C2H5), a silicon-bonded propyl group (Si-C3H7), a silicon-bonded butyl group (Si-C4H9), a silicon-bonded pentyl group (Si-C5H 11 ), hexyl group bonded to silicon atom (Si-C6H 13 ), or the presence / absence of signals of phenyl groups bonded to silicon atoms (Si-C6H5).

[0363] Measuring method of content of organic silicon polymer fine particles contained in toner

[0364] The content of the organic silicon polymer fine particles contained in the toner can be determined using the following method. 1 g of the toner is put into a vial, and dissolved and dispersed in 31 g of chloroform. A dispersion is prepared by treating with an ultrasonic homogenizer for 30 minutes to effectively disperse.

[0365] Ultrasonic treatment equipment: VP-050 ultrasonic homogenizer (available from Taitec Corporation)

[0366] Microchip: Stepped microchip, tip diameter 2mmφ

[0367] Microchip tip position: Center of glass vial, 5 mm above the bottom of the vial

[0368] Ultrasonication conditions: 30% intensity, 30 minutes; during this treatment, ultrasonic waves were applied while cooling the vial with ice water to prevent the dispersion from heating up.

[0369] The dispersion was transferred to a glass tube (50 mL) for a swing rotor and centrifuged at 58.33S / cm3 using a centrifugal separator (H-9R, available from Kokusan Co., Ltd.). -1The organic silicon polymer fine particles in the glass tube were separated after centrifugation. These were extracted and dispersed again in 10 g of chloroform for washing, and the organic silicon polymer fine particles were separated using a centrifugal separator. After the washing step was performed again, the extracted organic silicon polymer fine particles were vacuum dried (24 hours, 40° C.) to remove the chloroform and separate the organic silicon polymer fine particles.

[0370] By measuring the weight of the separated sample, the content of the organic silicon polymer fine particles in the toner can be determined.

[0371] In addition, in the case where the toner contains other external additives such as silica fine particles in addition to the organic silicon polymer fine particles, by performing the above-mentioned centrifugal separation, it is possible to separate them by means of specific gravity difference. In addition, by performing the above-mentioned ultrasonic treatment and centrifugal separation, toner particles from which the external additives have been removed can be obtained. The obtained toner particles can be used in various analyses.

[0372] In the case where it is difficult to separate the silicone polymer fine particles by specific gravity, the content can be determined by determining the volume ratio of each particle in the separated mixture. SEM-EDX is used to determine the volume ratio of each particle in the separated mixture. In addition, in the case where particles such as silicone polymer fine particles and silica fine particles have similar compositions, the silicone polymer fine particles and silica fine particles are distinguished by SEM-EDX. This method is described later.

[0373] Measuring method of content of silica fine particles contained in toner

[0374] The content of the silica fine particles contained in the toner can be determined using the following method.

[0375] 1 g of the toner is put into a vial, and dissolved and dispersed in 31 g of chloroform. A dispersion is prepared by treating with an ultrasonic homogenizer for 30 minutes to effectively disperse.

[0376] Ultrasonic treatment equipment: VP-050 ultrasonic homogenizer (available from Taitec Corporation)

[0377] Microchip: Stepped microchip, tip diameter 2mmφ

[0378] Microchip tip position: Center of glass vial, 5 mm above the bottom of the vial

[0379] Ultrasonication conditions: 30% intensity, 30 minutes; during this treatment, ultrasonic waves were applied while cooling the vial with ice water to prevent the dispersion from heating up.

[0380] The dispersion was transferred to a glass tube (50 mL) for a swing rotor and centrifuged at 58.33S / cm3 using a centrifugal separator (H-9R, available from Kokusan Co., Ltd.). -1 The silica fine particles in the glass tube were separated after centrifugation at a rate of 1000 g for 30 minutes. These were extracted and dispersed again in 10 g of chloroform for washing, and the silica fine particles were separated using a centrifuge. After the washing step was performed again, the extracted silica fine particles were vacuum dried (24 hours, 40° C.) to remove the chloroform and separate the silica fine particles.

[0381] By measuring the weight of the separated sample, the content of the silica fine particles in the toner can be determined.

[0382] In addition, the method for distinguishing the silicone polymer fine particles from the silica fine particles is as follows.

[0383] Identification of Silicone Polymer Fine Particles and Silica Fine Particles

[0384] In the case where the toner contains silicone polymer fine particles and silica fine particles, these can be distinguished using the following method.

[0385] As a method of identifying the organic silicon polymer fine particles and the silica fine particles contained in the toner, a combination of shape observation using SEM and elemental analysis using EDX may be used.

[0386] The toner was observed in a field of view magnified up to 50,000 times using an S-4800 scanning electron microscope (manufactured by Hitachi, Ltd.). The microscope was focused on the toner particle surface, and the external additive was observed. The particles of the external additive were subjected to EDX analysis, and whether the analyzed particles were organic silicon polymer fine particles was evaluated by the presence / absence of Si element peaks.

[0387] In the case where the toner contains both silicone polymer fine particles and silica fine particles, the silicone polymer fine particles are identified by comparing the ratio of the Si and O element content values ​​(atomic %) (Si / O ratio). Standard samples of silicone polymer fine particles and silica fine particles are subjected to EDS analysis under the same conditions, and the Si and O element content values ​​(atomic %) are obtained. The Si / O ratio of the silicone polymer fine particles is represented by A, and the Si / O ratio of the silica fine particles is represented by B. The measurement conditions are selected so that the value of A is significantly greater than the value of B. Specifically, the standard sample is measured 10 times under the same conditions, and the arithmetic mean of A and B is obtained. The measurement conditions are selected so that the average value obtained is A / B>1.1.

[0388] In the case where the Si / O ratio of the fine particles to be distinguished is further toward A than [(A+B) / 2], the fine particles in question are evaluated to be organic silicon polymer fine particles.

[0389] Tospearl 120A (produced by Momentive Performance Materials Inc.) was used as a standard sample of silicone polymer fine particles, and HDK V15 (produced by Asahi Kasei Corporation) was used as a standard sample of silica particles.

[0390] Example

[0391] The present invention is described more specifically below using Production Examples and Examples, but the present invention is by no means limited to or by these. Unless otherwise specifically stated, "parts" and "%" given in Examples and Comparative Examples are based on mass in all cases.

[0392] Synthesis of polyester resin (A-1)

[0393] The polyester resin (A-1) was synthesized using the following procedure.

[0394] The following materials were introduced into an autoclave equipped with a decompression device, a water separation device, a nitrogen introduction device, a temperature measurement device, and a stirring device, and a reaction was performed under a nitrogen atmosphere at normal pressure at 200° C. for 5 hours.

[0395] Bisphenol A propylene oxide 2.0 mol adduct: 77.4 parts

[0396] Terephthalic acid: 15.8 parts

[0397] Isophthalic acid: 15.8 parts

[0398] Maleic acid: None

[0399] Tetrabutoxy titanate: 0.2 parts

[0400] After this, the following materials were added and reacted at 220° C. for 3 hours.

[0401] Trimellitic acid: 0.1 part

[0402] Tetrabutoxy titanate: 0.3 parts

[0403] The reaction was further carried out under reduced pressure of 10 mmHg to 20 mmHg for 2 hours. The obtained resin was dissolved in chloroform, the solution was added dropwise to ethanol, and then precipitated and filtered to obtain a polyester resin (A-1). The Mw value of the obtained polyester resin (A-1) was 10,200.

[0404] Synthesis of polyester resins (A-2) to (A-6)

[0405] Polyester resins (A-2) to (A-6) were obtained in the same manner as in the synthesis of polyester resin (A-1), except that propylene oxide 2.0 mol adduct of bisphenol A, terephthalic acid, isophthalic acid, maleic acid and trimellitic acid were changed to the components and parts shown in Table 1. The Mw values ​​of the obtained polyester resins were as follows.

[0406] (A-2): Mw = 19,500

[0407] (A-3): Mw = 20,100

[0408] (A-4): Mw = 21,000

[0409] (A-5): Mw = 23,000

[0410] (A-6): Mw = 19,400

[0411] Synthesis of Resin A (R-1)

[0412] Resin A (R-1) was synthesized using the following procedure.

[0413] Resin A (R-1) is synthesized in the following manner by amidating the carboxyl group in the polyester resin (A-2) and the amino group in the aminosilane.

[0414] 100.0 parts of polyester resin (A-2) was dissolved in 400.0 parts of N,N-dimethylacetamide, and the following materials were added thereto and stirred at normal temperature for 5 hours. After the reaction was completed, resin A (R-1) was obtained by dropping the solution into methanol, reprecipitating and filtering.

[0415] Silane compound: 3-aminopropyltrimethoxysilane: 1.2 parts

[0416] Condensation agent: DMT-MM (4-(4,4-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride): 2.4 parts

[0417] The obtained resin A (R-1) had a silicon concentration of 0.20 mass % and an Mw value of 19,700.

[0418] Synthesis of Resins A (R-2) to (R-11) and (R-14)

[0419] Resins A (R-2) to (R-11) and (R-14) were obtained in the same manner as in the synthesis of Resin A (R-1), except that the polyester resin, silane compound and condensing agent were changed to the components and parts shown in Table 2. The physical properties are shown in Table 2.

[0420] Synthesis of Resin A (R-12)

[0421] Resin A (R-12) was synthesized using the following procedure.

[0422] Resin A (R-12) is synthesized in the following manner by reacting a hydroxyl group in the polyester resin (A-2) with an isocyanate group in an isocyanatosilane to form a urethane bond.

[0423] 100.0 parts of polyester resin (A-2) was dissolved in 1,000.0 parts of chloroform, and the following materials were added thereto under a nitrogen atmosphere and stirred at normal temperature for 5 hours. After the reaction was completed, resin A (R-12) was obtained by dropping the solution into methanol, reprecipitating and filtering.

[0424] ·3-isocyanatopropyldimethylmethoxysilane: 1.2 parts

[0425] Titanium (IV) tetraisopropoxide: 1.0 part

[0426] The physical properties of the obtained (R-12) are shown in Table 2.

[0427] Synthesis of Resin A (R-13)

[0428] Resin A (R-13) was synthesized using the following procedure.

[0429] The silane-modified polyester resin A (R-13) is synthesized in the following manner by forming a linking group represented by the following formula (14) or (15) through a reaction for inserting an epoxy group in epoxysilane into an ester bond in the polyester resin (A-2).

[0430] 100.0 parts of polyester resin (A-2) was dissolved in 200.0 parts of anisole, and the following materials were added thereto in a nitrogen atmosphere and stirred at about 140° C. for 5 hours. After cooling, the reaction mixture was dissolved in 200 mL of chloroform, added dropwise to methanol, reprecipitated and filtered, thereby obtaining resin A (R-13).

[0431] Silane compound: 5,6-epoxyhexyltrimethoxysilane: 1.3 parts

[0432] Catalyst: Tetrabutylphosphonium bromide: 10.0 parts

[0433] The physical properties of the obtained (R-13) are shown in Table 2.

[0434]

[0435] Synthesis of Resin A (R-15)

[0436] Resin A (R-15) was synthesized using the following procedure.

[0437] By introducing silane into the double bonds in the polyester resin (A-6) by means of a vinyl polymerization reaction, a silane-modified polyester resin A (R-15) was synthesized in the following manner.

[0438] 100.0 parts of polyester resin (A-6) was dissolved in 1,000.0 parts of toluene, 1.5 parts of 3-methacryloxypropyldimethylmethoxysilane and 0.6 parts of tert-butyl peroxybenzoate [produced by NOF Corp., trade name: Perbutyl Z] were added thereto in a nitrogen atmosphere, and a reaction was performed at 100° C. for 5 hours. Resin A (R-15) was obtained by reprecipitating the obtained solution in methanol, filtering, washing and vacuum drying. The obtained (R-15) had a silicon concentration of 0.20 mass % and an Mw value of 19,600.

[0439] Preparation of silica fine particles 1

[0440] 687.9 g of methanol, 42.0 g of pure water and 42.0 g of 28% by mass ammonia water were placed in a 3-liter glass reactor equipped with a stirrer, a dropping funnel and a thermometer, and mixed. The obtained solution was adjusted to a temperature of 35° C., and while stirring, 1,100.0 g (7.23 mol) of tetramethoxysilane and 395.2 g of 5.4% by mass ammonia water were simultaneously added. Tetramethoxysilane was added dropwise over a period of 5.0 hours, and ammonia water was added dropwise over a period of 4 hours.

[0441] After the dropwise addition was completed, a methanol-water dispersion of hydrophilic spherical sol-gel silica fine particles was obtained by conducting hydrolysis with continuous stirring for 0.2 hours.

[0442] Next, an ester adapter and a cooling tube were connected to a glass reactor, and methanol was distilled off by heating the dispersion to 65° C. Then, pure water was added in an amount equivalent to the methanol removed by distillation. The dispersion was dried at 80° C. under reduced pressure. The obtained silica fine particles were heated in a constant temperature bath at 400° C. for 10 minutes. The obtained silica fine particles (untreated silica) were crushed using a pulverizer (produced by Hosokawa Micron Corp.).

[0443] 50g of silica fine particles were loaded into a polytetrafluoroethylene inner cylinder stainless steel autoclave with an internal volume of 1,000mL. After replacing the interior of the autoclave with nitrogen, 0.5g of hexamethyldisilazane and 0.1g of water were uniformly sprayed on the silica fine particles in a mist form while rotating the stirring blade connected to the autoclave at 400rpm. After stirring for 30 minutes, the autoclave was sealed and heated at 200°C for 2 hours. Then, silica fine particles 1 were obtained by deamination by decompressing the system while continuously heating. The number average primary particle size of the silica fine particles 1 obtained was 100nm, and the SF-1 value was 110 and the SF-2 value was 115. The physical properties are shown in Table 3.

[0444] Preparation of Silica Fine Particles 2 to 8

[0445] Silica fine particles 2 to 8 were obtained in the same manner as in the preparation of silica fine particle 1, except that the amount of 28% by mass ammonia water was changed to the amount shown in Table 3, and the dropping time of tetramethoxysilane and the stirring duration after the completion of the dropping were changed to the conditions shown in Table 3. The physical properties are shown in Table 3.

[0446] Preparation of organosilicon polymer fine particles 1

[0447] The silicone polymer fine particles 1 were prepared using the following procedure.

[0448] Step 1

[0449] 360 parts of water were placed in a reaction vessel equipped with a thermometer and a stirrer, and 17 parts of hydrochloric acid having a concentration of 5.0% by mass were added thereto to form a uniform solution. While stirring the uniform solution at a temperature of 25° C., 136 parts of methyltrimethoxysilane were added thereto and stirred for 5 hours, after which the solution was filtered to obtain a transparent reaction solution containing a silanol compound or a partial condensate thereof.

[0450] Step 2

[0451] 540 parts of water were put into a reaction container equipped with a thermometer and a stirrer, and a dropping device, and 19 parts of ammonia water having a concentration of 10.0% by mass were added to obtain a uniform solution. While stirring the uniform solution at a temperature of 30° C., 100 parts of the reaction solution obtained in the first step were added dropwise over 0.60 hours, and stirring was performed for 6 hours to obtain a suspension. The resulting suspension was treated with a centrifugal separator and fine particles were precipitated and recovered, and dried with a dryer at a temperature of 180° C. for 24 hours to obtain silicone polymer fine particles 1.

[0452] When conducting 29In Si-NMR measurement, the ratio of the area of ​​the peak derived from silicon having a T3 unit structure to the total area of ​​the peaks of all silicon elements contained in the organic silicon polymer fine particles (T3 unit structure peak area ratio) is 1.00. In addition, the number average primary particle size is 90nm, the SF-1 value is 106, and the SF-2 value is 110. The physical properties are shown in Table 4.

[0453] Preparation of Silicone Polymer Fine Particles 2 to 13

[0454] Silicone polymer fine particles 2 to 13 were obtained in the same manner as in the preparation of silicone polymer fine particle 1, except that methyltrimethoxysilane was changed to the alkoxysilane component and the number of parts shown in Table 4, and the production conditions were changed to those shown in Table 4. The physical properties are shown in Table 4.

[0455] [Table 1]

[0456] Table 1. Resin A

[0457] PO2.0mol adduct of bisphenol A Terephthalic acid Isophthalic acid Maleic acid Trimellitic acid A-1 77.4 parts by mass 15.8 parts by mass 15.8 parts by mass - 0.1 parts by mass A-2 77.4 parts by mass 15.8 parts by mass 15.8 parts by mass - 1.0 parts by mass A-3 77.1 parts by mass 15.0 parts by mass 15.0 parts by mass - 3.0 parts by mass A-4 76.5 parts by mass 13.3 parts by mass 13.3 parts by mass - 6.9 parts by mass A-5 75.1 parts by mass 10.0 parts by mass 9.2 parts by mass - 15.5 parts by mass A-6 77.8 parts by mass 15.1 parts by mass 15.1 parts by mass 1.1 parts by mass 1.0 parts by mass

[0458] *PO: Propylene oxide

[0459] [Table 2]

[0460] Table 2. Resin A

[0461]

[0462] In the table, -OMe represents a methoxy group, -Me represents a methyl group, -OEt represents an ethoxy group, and -Ph- represents a phenylene group. The silicon concentration represents the content of silicon atoms in the resin A (mass %).

[0463] [Table 3]

[0464] Table 3. Formulation of silica particles

[0465]

[0466] In the tables, the particle size indicates the number average primary particle size.

[0467] [Table 4]

[0468] Table 4. Formulation of silicone polymer fine particles

[0469]

[0470]

[0471] *The numerical values ​​of alkoxysilane, water, hydrochloric acid, the reaction solution obtained in the first step, and aqueous ammonia indicate the added parts thereof.

[0472] Production of toner particles 1

[0473] Production of water-based media 1

[0474] 390.0 parts of deionized water and 14.0 parts of sodium phosphate (dodecahydrate) (RASA Industries, Ltd.) were put into the reactor, and kept at 65° C. for 1.0 hour while purging with nitrogen.

[0475] While stirring at 12,000 rpm using a TK homomixer (Tokushu Kika Kogyo Co., Ltd.), a calcium chloride aqueous solution in which 9.2 parts of calcium chloride (dihydrate) was dissolved in 10.0 parts of deionized water was added at once to prepare an aqueous medium containing a dispersion stabilizer.

[0476] 10% hydrochloric acid was put into the aqueous medium to adjust the pH to 6.0 and obtain an aqueous medium 1.

[0477] Production of polymerizable monomer composition 1

[0478] Styrene: 60 parts

[0479] Colorant (CI Pigment Blue 15:3): 6.5 parts

[0480] Dispersion liquid 1 in which a colorant is dispersed is prepared by charging the above-listed materials into an attritor (produced by Nippon Coke and Engineering Co., Ltd.), and then dispersing at 220 rpm for 5.0 hours using zirconium oxide particles having a diameter of 1.7 mm.

[0481] The following materials were added to this dispersion 1.

[0482]

[0483] This was then maintained at 65° C. and dissolved and dispersed to be uniform using a TK homomixer at 500 rpm to prepare a polymerizable monomer composition 1.

[0484] Granulation step

[0485] While the temperature of aqueous medium 1 was maintained at 70°C and the rotation speed of the stirrer was maintained at 12,000 rpm, polymerizable monomer composition 1 was added to aqueous medium 1, and 9.0 parts of polymerization initiator tert-butyl peroxypivalate was added. Granulation was performed for 10 minutes while the stirrer was maintained at 12,000 rpm.

[0486] Polymerization step

[0487] The high-speed stirrer was replaced with a stirrer equipped with a propeller blade, and polymerization was performed for 5.0 hours while maintaining 70° C. and stirring at 150 rpm. A further polymerization reaction was performed by raising the temperature to 85° C. and heating for 2.0 hours to obtain a toner particle dispersion liquid 1.

[0488] Washing and filtration steps

[0489] The pH was then adjusted to 1.5 with 1 mol / L hydrochloric acid; stirring was subsequently performed for 1 hour; and filtration was performed while washing with deionized water to obtain Toner Particles 1 .

[0490] Production of toner particles 2

[0491] Toner Particles 2 were produced in the same manner as Toner Particles 1 except that Resin A (R-1) and Polyester Resin (A-1) were changed as shown below.

[0492] Resin A (R-1) 0.1 part

[0493] Polyester resin (A-1) 7.9 parts

[0494] Production of toner particles 3

[0495] Toner Particles 3 were produced in the same manner as Toner Particles 1 except that Resin A (R-1) and Polyester Resin (A-1) were changed as shown below.

[0496] Resin A (R-1) 3.0 parts

[0497] ·Polyester resin (A-1) 5.0 parts

[0498] Production of toner particles 4

[0499] Toner Particles 4 were produced in the same manner as Toner Particles 1 except that Resin A (R-1) and Polyester Resin (A-1) were changed as shown below.

[0500] Resin A (R-1) 7.0 parts

[0501] ·Polyester resin (A-1) 1.0 part

[0502] Production of Toner Particles 5

[0503] Toner Particles 5 were produced in the same manner as Toner Particles 1 except that Resin A (R-1) and Polyester Resin (A-1) were changed as shown below.

[0504] Resin A (R-1) 10.0 parts

[0505] ·Polyester resin (A-1) 1.0 part

[0506] Production of Toner Particles 6 to 11, 24 and 25

[0507] Toner particles 6 to 11, 24 and 25 were produced in the same manner as toner particle 1, except that resin A (R-1) was changed to resins A (R-2) to (R-7), (R-13) and (R-14).

[0508] Production of Toner Particles 12

[0509] Toner Particles 12 are produced in the same manner as Toner Particles 1 except that the amount of behenyl behenate wax is changed to 0 parts.

[0510] Production of toner particles 16 to 20

[0511] Toner Particles 16 to 20 were produced in the same manner as Toner Particle 1, except that the amount of behenyl behenate wax was changed to 0 parts and Resin A (R-1) was changed to Resins A (R-8) to (R-12).

[0512] Production of Toner Particles 13

[0513] Production of resin particle dispersion 1

[0514] The following materials were weighed and mixed and dissolved.

[0515]

[0516] A 10% aqueous solution of Neogen RK (DKS Co., Ltd.) was added to the resulting solution and dispersed. An aqueous solution of 0.15 parts of potassium persulfate dissolved in 10.0 parts of deionized water was added while slowly stirring for 10 minutes. After purging with nitrogen, emulsion polymerization was performed at a temperature of 70° C. for 6.0 hours.

[0517] After the polymerization was completed, the reaction solution was cooled to room temperature and deionized water was added to obtain a resin particle dispersion having a solid concentration of 12.5% ​​and a volume-based median particle diameter of 0.2 μm.

[0518] Production of resin particle dispersion 2

[0519] Resin particle dispersion 2 was obtained in the same manner as in Resin particle dispersion 1 except that resin A (R-1) was not added.

[0520] Production of wax particle dispersions

[0521] Weigh the following materials and mix.

[0522] Fischer-Tropsch wax (melting point: 78°C) 100.0 parts

[0523] Neogen RK (DKS Co., Ltd.) 15.0 copies

[0524] ·385.0 parts of deionized water

[0525] These materials were dispersed for 1 hour using a JN100 wet jet mill (Jokoh Co., Ltd.) to obtain a wax particle dispersion. The solid concentration of the wax in the wax particle dispersion was 20.0%.

[0526] Production of colorant particle dispersions

[0527] Weigh the following materials and mix.

[0528] Colorant (CI Pigment Blue 15:3) 100.0 parts

[0529] Neogen RK (DKS Co., Ltd.) 15.0 copies

[0530] 885.0 parts of deionized water

[0531] These materials were dispersed for 1 hour using a JN100 wet jet mill (Jokoh Co., Ltd.) to obtain a colorant particle dispersion.

[0532] Aggregate particle formation

[0533]

[0534] These materials were dispersed using a homogenizer (Ultra-Turrax T50, IKA Works GmbH & Co. KG) and then heated to 65° C. while stirring.

[0535] After stirring at 65° C. for 1.0 hour, 20.0 parts of the resin particle dispersion 1 was added, and stirring was further performed for 0.2 hour. The formation of aggregate particles having a number average particle diameter of 7.0 μm was confirmed by observation with an optical microscope.

[0536] Then, 2.2 parts of Neogen RK (DKS Co., Ltd.) was added thereto, followed by heating to 80° C. and stirring for 2.0 hours to obtain fused spherical toner particles.

[0537] Cooling was performed, followed by filtration, and the separated solid was washed with 720.0 parts of deionized water for 1.0 hour by stirring. The solution containing the toner particles was filtered, and toner particles 13 were obtained by drying using a vacuum dryer.

[0538] Production of Toner Particles 14

[0539] Those parts of the process of producing the toner particles 13 starting from the formation of aggregate particles are changed as follows.

[0540]

[0541] The materials listed above were dispersed using a homogenizer (Ultratarax T50 manufactured by IKA), and then heated to 65° C. while stirring.

[0542] When observed with an optical microscope after stirring at 65° C. for 1.2 hours, it was confirmed that aggregate particles having a number average particle diameter of 7.0 μm were formed.

[0543] After 2.2 parts of Neogen RK (produced by Dai-ichi Kogyo Seiyaku Co., Ltd.) was added thereto, fused spherical toner particles were obtained by heating to 80° C. and stirring for 2.0 hours.

[0544] The solid obtained by cooling, filtering and filtering out was stirred and washed with water using 720.0 parts of ion exchange water for 1.0 hour.Toner particles 14 were obtained by filtering the solution containing the toner particles and drying it using a vacuum dryer.

[0545] Production of Toner Particles 15

[0546] The following materials were placed in a reactor equipped with a condenser, a stirrer, and a nitrogen inlet tube.

[0547] ·29.0 parts of terephthalic acid

[0548] · Polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane 80.0 parts

[0549] 0.1 part of dihydroxybis(triethanolamine)titanium

[0550] It was then heated to 200°C and reacted for 9 hours while introducing nitrogen and removing generated water. Polyester resin (A-7) was synthesized as a binder resin by adding 5.8 parts of trimellitic anhydride, heating to 170°C and reacting for 3 hours.

[0551]

[0552]

[0553] In addition, the above-listed materials were charged into an autoclave, the system was purged with nitrogen, and the temperature was maintained at 180° C. while stirring. 50.0 parts of a 2.0% xylene solution of tert-butyl hydroperoxide was continuously added dropwise to the system over 4.5 hours, and after cooling, the solvent was separated and removed to obtain a graft polymer in which the copolymer was grafted on polyethylene.

[0554]

[0555] These materials were thoroughly mixed using an FM mixer (Model FM-75, Nippon Coke & Engineering Co., Ltd.), and then melt-kneaded using a twin-screw kneader (Model PCM-30, Ikegai Ironworks Corporation) set at a temperature of 100°C.

[0556] The obtained kneaded material was cooled and coarsely pulverized to 1 mm or less using a hammer mill to obtain a coarsely pulverized product. Then, a finely pulverized material of about 5 μm was obtained from the coarsely pulverized product using Turbo Mill (T-250: RSS rotor / SNB liner) from Turbo Kogyo Co., Ltd.

[0557] The fine powder and the coarse powder are then cut using a multi-classifier based on the Coanda effect to obtain toner particles 15 .

[0558] Production of Toner Particles 21

[0559] Toner Particles 21 are produced in the same manner as Toner Particles 1 except that Resin A (R-1) is changed to Resin A (R-15).

[0560] Production of Toner Particles 22

[0561] Toner Particles 22 were produced in the same manner as Toner Particles 1 except that Resin A (R-1) was changed to 0.2 parts of 3-methacryloxypropyldimethylmethoxysilane.

[0562] Production of Toner Particles 23

[0563] The production process of the wax particle dispersion in the production of the toner particles 13 was changed in the following manner.

[0564] 70.0 parts of Fischer-Tropsch wax (melting point: 78° C.) and 30.0 parts of behenyl behenate (melting point: 74° C.) were used instead of 100.0 parts of Fischer-Tropsch wax (melting point: 78° C.).

[0565] Additionally, those parts of the processes starting with aggregate particle formation were changed as shown below.

[0566]

[0567] The materials listed above were dispersed using a homogenizer (Ultratarax T50 manufactured by IKA), and then heated to 65° C. while stirring.

[0568] When observed with an optical microscope after stirring at 65° C. for 1.2 hours, it was confirmed that aggregate particles having a number average particle diameter of 7.0 μm were formed.

[0569] After 2.2 parts of Neogen RK (produced by Dai-ichi Kogyo Seiyaku Co., Ltd.) was added thereto, fused spherical toner particles were obtained by heating to 80° C. and stirring for 2.0 hours.

[0570] The solid obtained by cooling, filtering and filtering out was stirred and washed with water using 720.0 parts of ion exchange water for 1.0 hour.Toner particles 23 were obtained by filtering the solution containing the toner particles and drying it using a vacuum dryer.

[0571] When the toner particles obtained using the above method were evaluated using TOF-SIMS, it was confirmed that the Si-containing resin A was present in the surface layer in the toner particles 1 to 22 , 24 , and 25 .

[0572] Production of toner 1

[0573] Toner 1 was obtained by mixing 100 parts of Toner Particles 1, 1.0 part of Silica Fine Particles 1 and 1.0 part of Silicone Polymer Fine Particles 1 in a Henschel Mixer (manufactured by Mitsui Miike Kakoki Corporation) for 5 minutes. The temperature of the Henschel Mixer jacket was set to 10° C. and the peripheral speed of the rotating blade was 38 m / sec.

[0574] Production of Toners 2 to 44 and Comparative Toners 1 to 6

[0575] These were produced in the same manner as in the production of Toner 1, except that Toner Particle 1 was replaced with Toner Particles 2 to 25, Silica Fine Particle 1 was replaced with Silica Fine Particles 2 to 8, and Silicone Polymer Fine Particle 1 was replaced with Silicone Polymer Fine Particles 2 to 13 as shown in Table 5. The number of parts of the external additives was changed as shown in Table 5. R-972 (number average primary particle diameter: 18 nm, SF-1: 150, SF-2: 160) produced by Nippon Aerosil Co. Ltd. was used as the fumed silica used in Comparative Toner 1. Toners 2 to 44 and Comparative Toners 1 to 6 were obtained in the same manner as in the production of Toner 1, except for these changes.

[0576] Evaluation of initial image streaks and image streaks after long-term use

[0577] Image streaks are longitudinal streaks having a size of about 0.5 mm and are produced by detachment of silicone polymer fine particles, and these are image defects that are easily observed when an entire surface halftone image is output.

[0578] A modified LBP712Ci (produced by Canon Inc.) was used as the image forming apparatus. The process speed of the apparatus was modified to 250 mm / sec. In addition, necessary adjustments were made so that image formation was possible under these conditions. In addition, the toner was removed from the black and cyan cartridges and replaced with 50 g of each toner to be evaluated. The toner loading was 1.0 mg / cm 2 .

[0579] Image streaks were evaluated during continuous use in a normal temperature and humidity environment (23°C, 60% RH). XEROX 4200 paper (produced by XEROX, 75 g / m 2 ) is used as evaluation paper.

[0580] Under normal temperature and humidity conditions, 1,000 sheets of intermittent continuous use were performed, two E-shaped images were output every 4 seconds at 1% image coverage, and then a 50% halftone image was output on the entire sheet, and the presence or absence of streaks was observed. The evaluation result at this time was taken as initial image streaks (initial streaks).

[0581] In addition, after intermittently printing another 14,000 sheets, a 50% halftone image was output on the entire sheet, and the presence or absence of streaks was observed. The evaluation result at this time was taken as image streaks after long-term use (streaks after long-term use).

[0582] A to C were judged as good.

[0583] Evaluation Criteria

[0584] A: No streaks or toner lumps.

[0585] B: No spotty streaks, but 1 to 2 small toner lumps.

[0586] C: There are 1 to 2 spot-like streaks at the edge portion, or there are 3 to 4 small toner lumps.

[0587] D: There are 1 to 2 spot-like streaks on the entire surface, or there are 5 to 6 small toner lumps.

[0588] E: There are 3 or more spot-like streaks on the entire surface, or there are 7 or more small toner lumps.

[0589] Evaluation of fogging after long-term use

[0590] The same image forming apparatus as that used for evaluating image streaks was used to evaluate fogging after continuous use in a normal temperature and humidity environment (23° C., 60% RH). XEROX 4200 paper (manufactured by XEROX, 75 g / m 2 ) is used as paper for long-term use.

[0591] Under normal temperature and humidity conditions, 15,000 sheets of intermittent continuous use were performed, and two E-shape images were output every 4 seconds at an image coverage of 1%.

[0592] Next, in glossy mode (1 / 3 speed), use letter-sized HP Brochure Paper 200g, Glossy (basis weight 200g / cm 2 ) was used as evaluation paper to print a solid white image with an image coverage of 0%. Using REFLECTMETER MODEL TC-6DS (produced by Tokyo Denshoku Co., Ltd.), the fog density (%) was calculated from the difference between the measured whiteness of the white background portion of the printed image and the whiteness of the transfer paper, and the image fogging (fogging after long-term use) was evaluated. An amber color filter was used as a color filter.

[0593] A lower value indicates a more favorable evaluation. The evaluation criteria are as follows.

[0594] A to C were judged as good.

[0595] Evaluation Criteria

[0596] A: Less than 1.0%

[0597] B: 1.0% or more and less than 2.0%

[0598] C: 2.0% or more and less than 3.0%

[0599] D: 3.0% or more

[0600] Evaluation of tape peelability

[0601] A color laser printer (HP Color LaserJet 3525dn, Hewlett-Packard Enterprise Development LP) modified to be able to adjust the developing bias voltage was used as an image forming apparatus, and FOX RIVER BOND paper (110 g / m 2 ) is used as a fixing medium.

[0602] A line image is used for the image in evaluation. By increasing the amount of toner on the image by setting a high image density by swinging the development bias, and by using thick paper having a large number of surface irregularities, it is possible to make melting of the toner in the concave portions in the paper and in the lower layer area of ​​the toner layer during the fixing step more difficult, thereby enabling strict evaluation of peeling.

[0603] The evaluation procedure is as follows. First, the image forming apparatus is left overnight in a low temperature and low humidity environment (15°C, 10% RH). When a low temperature is used for the evaluation environment, then the fixing unit is more difficult to warm up, and a strict evaluation can be performed.

[0604] Use FOX RIVER BOND paper, then adjust the development bias to give a line width of 180 μm to print the horizontal line image. After being placed under low temperature and low humidity for 1 hour, a polypropylene tape (Klebeband 19mm×10mm, from tesa SE) is attached to the horizontal line image and slowly peeled off. After peeling off, visually and microscopically observe the image and evaluate according to the following evaluation criteria. A to C are judged to be good. The evaluation results are shown in Table 6.

[0605] Evaluation Criteria

[0606] A: No missing

[0607] B: Slight loss was observed, but could not be identified by visual inspection

[0608] C: Slight visually identifiable defects observed

[0609] D: There are visually identifiable defects and the production line is cut

[0610] Evaluation of fixing winding

[0611] The same image forming apparatus as that used for evaluating image streaks was modified to be able to adjust the fixing temperature. GF-600 (manufactured by Canon Marketing Japan KK, 60 g / m 2 ) was used as evaluation paper. The output image was a full-page solid image, and the evaluation was performed under a normal temperature and humidity environment (23° C., 60% RH).

[0612] The fixing temperature was changed from 140° C. at intervals of 5° C. The toner was evaluated for fixing, and the paper feeding state at that time was visually confirmed. From the temperature of the fixing unit at which paper could be fed without winding, the fixing winding was evaluated based on the following criteria.

[0613] A to C were judged as good.

[0614] Evaluation Criteria

[0615] A: Below 150℃

[0616] B: 150℃ or higher and lower than 155℃

[0617] C: 155℃ or higher and lower than 160℃

[0618] D: 160℃ or above

[0619] [Table 5]

[0620]

[0621] In the table, "Si count" indicates the ion count derived from silicon having a mass number of 28, where the total ion count of ions having mass numbers of 1 to 1,800 in TOF-SIMS measurement of the toner particle surface is taken as 1.

[0622] [Table 6]

[0623] Table 6. Evaluation results

[0624]

[0625] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A toner comprising: Toner particles comprising resin A, and The external additive A is characterized in that The resin A is a resin represented by the following formula (1): The resin A is present on the surface of the toner particles, The external additive A is fine particles containing silicon, The average value of the shape factor SF-1 of the external additive A is 105 to 120, The shape factor SF-2 of the external additive A has an average value of 100 to 130, In formula (1), P 1 Indicates the polymer part, L 1 represents a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -OR 4 -、-NH-、-NHR 5 - or phenylene, R 4 and R 5 Each is independently an alkylene group or a phenylene group having 1 to 4 carbon atoms, and each carbon atom may have a hydroxyl group as a substituent; R 1 To R 3 At least one of them is hydroxyl or alkoxy, R 1 To R 3 The remainder of each independently represents a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, an aryl group or a hydroxyl group; m is a positive integer, and When the value of m is 2 or more, multiple L 1 Partial, multiple R 1 Partial, multiple R 2 Partial and Multiple R 3 The parts may be the same as or different from each other. 2 . The toner according to claim 1 , wherein the external additive A has a number average primary particle size of 30 nm to 300 nm.

3. The toner according to claim 1 or claim 2, wherein The content of the external additive A is 0.10 parts by mass to 6.00 parts by mass relative to 100 parts by mass of the toner particles. 4 . The toner according to claim 1 , wherein the external additive A contains silica fine particles.

5. The toner according to claim 1 or claim 2, wherein The external additive A comprises organic silicon polymer fine particles, The organic silicon polymer in the organic silicon polymer fine particles has a structure in which silicon atoms and oxygen atoms are alternately bonded. The organic silicon polymer has R a SiO 3 / 2 The T3 unit structure represented by R a represents an alkyl group having 1 to 6 carbon atoms or a phenyl group, and In the organosilicon polymer fine particles 29 In Si-NMR measurement, a ratio of an area of ​​a peak derived from silicon having the T3 unit structure to a total area of ​​peaks derived from all silicon elements contained in the organosilicon polymer in the organosilicon polymer fine particles is 0.70 to 1.

00. 6 . The toner according to claim 1 , wherein the toner particles contain an ester wax.

7. The toner according to claim 1 or claim 2, wherein P in formula (1) 1 It is a polyester part.

8. The toner according to claim 1 or claim 2, wherein L in formula (1) 1 is a structure represented by the following formula (3), In formula (3), * represents the bonding site with C=O, ** represents the bonding site with Si, and R 20 represents an alkylene group or a phenylene group having 1 to 4 carbon atoms, and each carbon atom may have a hydroxyl group as a substituent. 9 . The toner according to claim 1 , wherein the content of silicon atoms in the resin A is from 0.02% by mass to 2.00% by mass. 10 . The toner according to claim 1 , wherein the content of the resin A in the toner particles is 0.1% by mass to 10.0% by mass.

Citation Information

Patent Citations

  • Toner for electrostatic charge image development

    JP2017032598A

  • Toner for developing electrostatic

    CN1131284A

  • Toner for developing electrostatic image

    EP0716350A2